Anhydrous iron phosphate and preparation method thereof, positive electrode material and preparation method thereof, positive electrode plate and secondary battery
By controlling the particle grading of anhydrous iron phosphate, the problem of poor particle size distribution is solved, and the high compaction density and high charge and discharge efficiency of lithium iron phosphate positive electrode material are achieved.
Patent Information
- Application Number
- CN202411942055.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-04-15
AI Technical Summary
In the prior art, the particle size distribution of anhydrous iron phosphate is poor, resulting in the inability of lithium iron phosphate positive electrode material to take into account high compaction density and high charge and discharge efficiency.
By controlling the particle grading of anhydrous iron phosphate, the particle size is ensured to be distributed between 0.01 μm and 0.6 μm, accounting for 10%-30%, 50%-60%, 15%-30%, and 0.2%-10%, respectively, to achieve tight packing and high compaction density.
The dispersion of anhydrous iron phosphate and the reasonable particle size coordination are achieved, thereby improving the compaction density and charge and discharge efficiency of lithium iron phosphate positive electrode material.
Smart Images

Figure CN119822342A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of secondary batteries, and in particular to an anhydrous iron phosphate and a preparation method thereof, a positive electrode material and a preparation method thereof, a positive electrode sheet, and a secondary battery. Background Art
[0002] Lithium iron phosphate is a positive electrode material with high specific capacity, high energy, environmental friendliness and excellent safety performance. It has the characteristics of high theoretical specific capacity (2400mAh / g), low lithium insertion potential (3.4V), wide operating voltage range (3.4V~4.4V) and good safety performance. It has good application prospects in the fields of electric vehicles and energy storage.
[0003] However, in many energy storage applications, the compaction density (referred to as compaction) and charge and discharge efficiency (charge and discharge efficiency, referred to as energy efficiency) of lithium iron phosphate batteries still cannot meet user needs well. Compaction density is an important parameter to measure the compactness of lithium iron phosphate electrode materials, which is closely related to the volume energy density and cycle performance of the electrode. Charge and discharge efficiency refers to the energy conversion efficiency of the battery during the charging and discharging process. High charge and discharge efficiency means that the battery loses less energy during the charging and discharging process, which can improve the energy utilization rate and cycle life of the battery.
[0004] Increasing the compaction density of lithium iron phosphate is an effective means to increase the driving range. However, in the prior art, the compaction density is generally increased by increasing the sintering temperature or reducing the metal doping amount. Increasing the sintering temperature will cause the proportion of single crystal lithium iron phosphate to be too large, increasing polarization, and reducing the doping amount will cause the lithium ion diffusion rate to decrease, both of which will lead to reduced charging and discharging efficiency.
[0005] Lithium iron phosphate is generally produced by mixing anhydrous iron phosphate with a lithium source and sintering them. The performance of anhydrous iron phosphate has a greater impact on lithium iron phosphate. For example, when the particle size of anhydrous iron phosphate is too large, it will be difficult to dehydrate during the rotary kiln sintering process, resulting in low crystallinity of iron phosphate. During the sintering process of lithium iron phosphate, crystal transformation will occur to produce impurities, resulting in reduced electrical performance of lithium iron phosphate. If the particle size is too small, it will lead to primary particle agglomeration, reduced rinsing and impurity removal efficiency, high impurity content, and a high proportion of small particles during the sintering process, which is not conducive to the preparation of high-density products.
[0006] Therefore, the charge and discharge efficiency of high-compacted lithium iron phosphate in the prior art still has a large room for improvement. However, since the research on the key raw material anhydrous iron phosphate is mainly focused on the regulation of the iron-phosphorus ratio and the BET specific surface area, the electrical properties of lithium iron phosphate are mainly improved by increasing the iron-phosphorus ratio and reducing the BET specific surface area. However, the lithium iron phosphate prepared in this way tends to be small particles and long strips and sheet structures, and it is impossible to achieve a good particle grading, and the distribution packing density is low. The compaction density of lithium iron phosphate prepared by high iron-phosphorus ratio iron phosphate is generally low, the sand grinding of strip and sheet iron phosphate is difficult, the particles are irregular, the carbon coating effect of the prepared lithium iron phosphate is poor, the powder internal resistance is high, and the electrical performance is poor. Anhydrous iron phosphate with a small BET specific surface area is mainly achieved by increasing the sintering temperature of the rotary kiln, the sand grinding is difficult, the sintering temperature is high, and the discharge performance is poor. Therefore, the discharge performance of the currently prepared high-compacted lithium iron phosphate will decrease after the compaction density is increased. At present, there is no lithium iron phosphate material with high compaction density and high charge and discharge efficiency. Summary of the invention
[0007] In view of the technical problems existing in the background technology, the present application provides an anhydrous iron phosphate and a preparation method thereof, a positive electrode material and a preparation method thereof, a positive electrode sheet, and a secondary battery, aiming to solve the technical problem that the particle size distribution of anhydrous iron phosphate in the prior art is poor, which leads to the inability of lithium iron phosphate positive electrode materials to have both high compaction density and high charge and discharge efficiency.
[0008] In the first aspect, an embodiment of the present application provides an anhydrous ferric phosphate. In the primary particles of the anhydrous ferric phosphate, the number of particles with a particle size greater than or equal to 0.01 μm and less than 0.1 μm accounts for 10% to 30% by weight, the number of particles with a particle size of 0.1 μm to 0.2 μm accounts for 50% to 60%, the number of particles with a particle size greater than 0.2 μm and less than 0.4 μm accounts for 15% to 30%, and the number of particles with a particle size of 0.4 μm to 0.6 μm accounts for 0.2% to 10%.
[0009] In the technical solution of the embodiment of the present application, by controlling the particle grading within the above-mentioned range, an anhydrous iron phosphate with good dispersibility is obtained. The anhydrous iron phosphate with large and small particle sizes becomes the basis for preparing high-density positive electrode materials, ensuring the normal growth of lithium iron phosphate grains under high doping conditions, which is conducive to obtaining positive electrode materials with high compaction density, good rate performance, and high charging and discharging efficiency.
[0010] In some embodiments, the particle shape of anhydrous ferric phosphate is spherical, and the sphericity is 0.84-0.98; the tap density of anhydrous ferric phosphate is 0.93 g / cm 3 ~1.13g / cm 3 , compacted density is 1.57g / cm 3 ~1.61g / cm 3, the iron-phosphorus ratio is (0.957~0.970):1.
[0011] In this embodiment, the anhydrous iron phosphate has a higher sphericity and a higher tap density, indicating that the particle packing density is good and the particle size distribution is reasonable. The compaction density of the lithium iron phosphate prepared as the raw material is also relatively higher. Combined with a suitable iron-phosphorus ratio, it is beneficial to further improve the charging and discharging efficiency.
[0012] In a second aspect, the present application provides a method for preparing anhydrous ferric phosphate, comprising:
[0013] The ferrous source is mixed with the first dispersant to obtain a first raw material solution; the first phosphorus source is mixed with the second dispersant to obtain a second raw material solution;
[0014] The first raw material liquid, the second raw material liquid and the first oxidant are mixed, and after a first reaction treatment, a first mixture is obtained;
[0015] Adding a second phosphorus source to the first mixture, performing a second reaction treatment, and then adding a second oxidant to obtain a second mixture;
[0016] Adjusting the pH value and temperature of the second mixture, and obtaining anhydrous ferric phosphate after a third reaction treatment;
[0017] The first dispersant includes a cationic monomer and a coupling agent, and the second dispersant includes an anionic monomer and a chain transfer agent.
[0018] In the technical scheme of the embodiment of the present application, anhydrous ferric phosphate is prepared by a precipitation method, and the surface tension of the solution is reduced and the reaction rate is increased by the surfactant-like effect of the polymer formed by the first dispersant and the second dispersant. At the same time, the dispersion and complexation of the polymer are used to regulate the crystal morphology, and the step-by-step feeding of the oxidant and the phosphorus source is combined to regulate the reaction progress and control the iron-phosphorus ratio. The anhydrous ferric phosphate prepared has higher sphericity and more reasonable particle grading. Under the condition of a low proportion of large particles, the compaction density is significantly improved. The compaction density of lithium iron phosphate prepared from this anhydrous ferric phosphate is significantly increased, and the charge-discharge rate performance is better.
[0019] In some embodiments, the cationic monomer includes dimethyldiallylammonium chloride and / or acryloyloxyethyltrimethylammonium chloride; and / or, the coupling agent includes vinyltrimethoxysilane and / or 3-(methacryloyloxy)propyltrimethoxysilane; when the cationic monomer includes dimethyldiallylammonium chloride and acryloyloxyethyltrimethylammonium chloride, the mass ratio of dimethyldiallylammonium chloride to acryloyloxyethyltrimethylammonium chloride is 1:(2.5-3.5); and / or,
[0020] The anionic monomer includes one or more of methacrylic acid, itaconic acid and fumaric acid; and / or the chain transfer agent includes sodium hypophosphite and / or isopropanol; when the anionic monomer includes methacrylic acid and itaconic acid, the mass ratio of methacrylic acid to itaconic acid is 1:(2.5-3.5); when the anionic monomer includes methacrylic acid and fumaric acid, the mass ratio of methacrylic acid to fumaric acid is 1:(2.5-3.5); and / or the molar ratio of the cationic monomer to the coupling agent is 100:(20-35); and / or the molar ratio of the anionic monomer to the chain transfer agent is 100:(10-15).
[0021] In this embodiment, the cationic monomer and the anionic monomer are more conducive to the smooth polymerization to form a polymer with the assistance of a coupling agent and a chain transfer agent. The polymer is a surfactant-like polymer. After initially playing the role of dispersing ions, the polymer formed by the cationic monomer and the anionic monomer continues to disperse the crystal particles of iron phosphate. At the same time, the polymer formed by the anionic monomer and the cationic monomer further reduces the surface tension of the solution, better promotes the spherical growth of iron phosphate crystals, and improves the crystallinity of iron phosphate crystals, thereby improving the tap density of the anhydrous iron phosphate obtained.
[0022] In some embodiments, the molar ratio of the iron element in the ferrous source to the first dispersant is 1:(0.0125-0.0150); and / or, the molar ratio of the iron element in the ferrous source to the phosphorus element in the phosphorus source is 1:(0.9-1.1); and / or, the molar ratio of the phosphorus element in the phosphorus source to the second dispersant is 1:(0.0150-0.0170); and / or, the ferrous source is prepared by the following method: mixing a titanium dioxide byproduct having ferrous sulfate with water, heating and dissolving the mixture, adding 5%-15% ammonia water by mass for sedimentation, filtering and retaining the filtrate to obtain the ferrous source; and / or, independently, the first phosphorus source and the second phosphorus source are prepared by the following method: dissolving monoammonium phosphate with phosphoric acid and water and filtering the mixture, adding 5%-15% ammonia water by mass to the filtrate to adjust the pH value to 6-8.
[0023] In this embodiment, the above-mentioned ratio conditions are more conducive to the phosphate group to fully precipitate the iron ions, and further enhance the binding force between the positive charge of the cationic group from the cationic monomer in the polymer formed by the anionic monomer and the cationic monomer and the phosphate group, as well as the binding force between the anionic group from the anionic monomer in the polymer formed by the anionic monomer and the cationic monomer and the iron ions, thereby promoting the spherical growth of the particles and playing a better role in particle size regulation.
[0024] In some embodiments, the first oxidant includes hydrogen peroxide and / or sodium peroxide; and / or, the second oxidant includes hydrogen peroxide and / or sodium peroxide; and / or, the mass ratio of the first phosphorus source to the second phosphorus source is (15-25):(75-85); and / or, the molar ratio of the first oxidant to the iron element in the ferrous source is (0.6-1.1):1, and the molar ratio of the second oxidant to the iron element in the ferrous source is (2.1-2.8):1.
[0025] In this embodiment, the concentrations of the oxidant and reactants mentioned above are used together to regulate the reaction rate within a more suitable range; the step-by-step feeding is controlled by controlling the addition amounts of the first phosphorus source and the second phosphorus source, thereby controlling the generation and growth of iron phosphate, further improving the particle size distribution, and facilitating further improvement of the sphericity and dispersibility of anhydrous iron phosphate.
[0026] In some embodiments, in the first reaction treatment, the temperature is 40°C to 60°C, and the time is 0.5h to 1h; and / or, in the second reaction treatment, the temperature is 40°C to 60°C, and the time is 5min to 10min.
[0027] In this embodiment, the precipitation rate and dispersion effect of ferric phosphate are better within the above reaction temperature and time range, and the particle size distribution of anhydrous ferric phosphate particles is further improved.
[0028] In some embodiments, the steps of adjusting the pH value and temperature of the second mixture and obtaining anhydrous ferric phosphate after a third reaction treatment include: adjusting the temperature of the second mixture to 40°C to 60°C, controlling the pH value of the second mixture to 0.9 to 1.5, heating the mixture to 90°C to 95°C and reacting the mixture to a pH value of 1.6 to 2.0 to obtain a third mixture; and sequentially filtering, rinsing, flash evaporating, drying, crushing, and sieving the third mixture to obtain anhydrous ferric phosphate.
[0029] In this embodiment, by adjusting the temperature and pH value of the mixture within an appropriate range, the stable precipitation of iron phosphate is further controlled, and combined with pressure filtration, rinsing, flash evaporation, drying, crushing, and screening, anhydrous iron phosphate with high sphericity, good dispersibility, and good particle size grading is prepared, making the preparation method more practical.
[0030] In a third aspect, the present invention provides a positive electrode material, the general formula of which is LiFe 1-a-b- c Y a Ce b M c PO4@C, wherein M is one or more of tin, titanium, boron, and manganese, a is 0.007 to 0.013, b is 0.029 to 0.057, and c is 0.01 to 0.033; the mass fraction of C in the positive electrode material is 1.2% to 1.4%.
[0031] In this embodiment, the positive electrode material includes the above-mentioned anhydrous iron phosphate, and is doped and modified by three metal cations with different action mechanisms and proportions to refine the grains, combine with phosphate in the anhydrous iron phosphate to reduce the effect of phosphate on coarsening the grains, and ensure the initial structure of the iron phosphate and normal grain growth under high doping conditions. Therefore, it has the advantages of high compaction density, good rate performance, and high charging and discharging efficiency.
[0032] In some embodiments, the average primary particle size of the positive electrode material is 0.24 μm to 0.34 μm; wherein, in the positive electrode material, the number fraction of particles with an average primary particle size greater than or equal to 1 μm is less than or equal to 3.20%, and the compaction density is 2.52 g / cm 3 ~2.64g / cm 3 .
[0033] In this embodiment, the raw material can be anhydrous iron phosphate with a combination of large and small particle sizes, which can control the crystallization and growth process of lithium iron phosphate, further reduce the generation of large-particle single crystals in high-density lithium iron phosphate, and improve the compaction density and energy storage performance of the positive electrode material.
[0034] In a fourth aspect, an embodiment of the present application provides a method for preparing a positive electrode material, comprising the following steps:
[0035] The anhydrous ferric phosphate, lithium source, carbon source, complexing agent, dopant and water are mixed to obtain a mixed material;
[0036] The mixed material is sintered under a protective atmosphere to obtain a positive electrode material;
[0037] The dopants include yttrium oxide, cerium oxide and other oxides, and the other oxides include one or more of tin oxide, titanium oxide, boron oxide and manganese oxide.
[0038] In this embodiment, anhydrous iron phosphate with high crystallinity, low impurity content and excellent particle size distribution is used as a raw material, and the crystallization and growth process of lithium iron phosphate is controlled, which significantly reduces the generation of large-grained single crystals in high-density lithium iron phosphate. During the crystallization and growth of lithium iron phosphate, the chelating agent plays an inhibitory role before carbon coating, effectively avoiding the formation of crystal nuclei and reducing the generation of invalid single crystals during the growth of lithium iron phosphate particles. On the one hand, the effective proportion of high-efficiency lithium iron phosphate is guaranteed and the compaction density of lithium iron phosphate is improved; on the other hand, the good carbon coating effect of lithium iron phosphate and the low powder internal resistance and polarization are guaranteed, so that the positive electrode material has excellent charging performance, discharge performance and long-lasting cycle performance.
[0039] In some embodiments, the complexing agent includes glycerol and / or sodium gluconate; and / or, the dopant includes yttrium oxide, cerium oxide and other oxides, and the other oxides include one or more of tin dioxide, titanium dioxide, boron trioxide and manganese carbonate; the mass ratio of yttrium oxide, cerium oxide and other oxides is 1:(2-3):(1-2); and / or, the mass ratio of anhydrous ferric phosphate to the complexing agent is 1:(0.02-0.03); and / or, the mass ratio of anhydrous ferric phosphate to the dopant is 1:(0.008-0.009); and / or, the mass ratio of anhydrous ferric phosphate to the lithium source is 1:(1-1.05); and / or, the mass ratio of anhydrous ferric phosphate to the carbon source is 1:(0.09-0.11).
[0040] In this embodiment, the inhibitor combines with the active sites of the raw materials, reduces the generation of lithium iron phosphate single crystals, and improves the electrical performance of lithium iron phosphate. By controlling the raw material ratio within the above range, the waste of raw materials is reduced on the basis of more fully synthesizing lithium iron phosphate, thereby further reducing the preparation cost on the basis of maintaining the excellent electrical performance of lithium iron phosphate.
[0041] In some embodiments, the step of obtaining a positive electrode material after sintering the mixed material under a protective atmosphere includes: grinding the mixed material to obtain a ground material, and the D50 particle size of the ground material is 0.38μm~0.42μm; spray drying the ground material to obtain a spray material, and the D50 particle size of the spray material is 3.4μm~6.7μm; sintering the spray material under a protective atmosphere to obtain a positive electrode material; the sintering temperature is 760℃~820℃, and the time is 10h~18h.
[0042] In this embodiment, the anhydrous iron phosphate has high sphericity, good particle gradation, and a smaller particle size of the product after grinding and spray drying. By controlling the sintering temperature within an appropriate range, on the one hand, the compaction density can be increased, the lithium ion diffusion rate can be increased, and on the other hand, the proportion of single crystal lithium iron phosphate can be reduced, polarization can be reduced, and the lithium iron phosphate electrical performance can be better.
[0043] In a fifth aspect, an embodiment of the present application provides a positive electrode plate, comprising a positive electrode current collector and a positive electrode active layer disposed on at least one side of the positive electrode current collector, wherein the positive electrode active layer comprises the above-mentioned positive electrode material.
[0044] In this embodiment, the positive electrode plate includes the above-mentioned positive electrode material, and thus has the advantages of good rate performance and high charging and discharging efficiency.
[0045] In a sixth aspect, an embodiment of the present application provides a secondary battery, comprising the above-mentioned positive electrode plate.
[0046] In this embodiment, the secondary battery includes the above-mentioned positive electrode plate, and thus has the advantages of good rate performance and high charging and discharging efficiency.
[0047] The above description is only an overview of the technical solution of the present application. In order to more clearly understand the technical means of the present application, it can be implemented in accordance with the contents of the specification. In order to make the above and other purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are listed below. BRIEF DESCRIPTION OF THE DRAWINGS
[0048] In order to more clearly illustrate the technical solution of the present application, the following is a brief introduction to the drawings used in the present application. Obviously, the drawings described below are only some embodiments of the present application, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0049] Figure 1 This is a SEM image of anhydrous ferric phosphate prepared in Example 5 of the present application;
[0050] Figure 2 This is a SEM image of anhydrous ferric phosphate prepared in Comparative Example 5 of the present application;
[0051] Figure 3 XRD comparison diagram of anhydrous ferric phosphate prepared in Example 5 of the present application and Comparative Example 5;
[0052] Figure 4 This is a SEM particle size analysis diagram of anhydrous ferric phosphate prepared in Example 5 of the present application;
[0053] Figure 5 This is a SEM particle size analysis diagram of the anhydrous ferric phosphate prepared in Comparative Example 5 of the present application. DETAILED DESCRIPTION
[0054] The following embodiments of the technical solution of the present application are described in detail in conjunction with the accompanying drawings. The following embodiments are only used to more clearly illustrate the technical solution of the present application, and are therefore only used as examples, and cannot be used to limit the scope of protection of the present application.
[0055] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" in the specification and claims of this application and the above-mentioned figure descriptions and any variations thereof are intended to cover non-exclusive inclusions.
[0056] In the description of the embodiments of the present application, the technical terms "first", "second", etc. are only used to distinguish different objects, and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features. In the description of the embodiments of the present application, the meaning of "multiple" is more than two, unless otherwise clearly and specifically defined.
[0057] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.
[0058] In the description of the embodiments of the present application, the term "and / or" is only a description of the association relationship of associated objects, indicating that three relationships may exist. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.
[0059] In the description of the embodiments of the present application, the term "multiple" refers to more than two (including two). Similarly, "multiple groups" refers to more than two groups (including two groups), and "multiple pieces" refers to more than two pieces (including two pieces).
[0060] In the description of the embodiments of the present application, unless otherwise specified, the solvent used in the raw material liquid, reaction liquid, solution, etc. is selected from at least one of deionized water, distilled water, pure water, and ultrapure water. Similarly, in the description of the embodiments of the present application, unless otherwise specified, "water" is selected from at least one of deionized water, distilled water, pure water, and ultrapure water.
[0061] At present, the main way to increase the compaction density of lithium iron phosphate is to increase the sand grinding particle size and the finished product particle size, but these ways will lead to a decrease in the electrical performance of lithium iron phosphate, especially the charge and discharge performance. A feasible method is to reduce the BET specific surface area of the key raw material anhydrous iron phosphate, but anhydrous iron phosphate with a small BET specific surface area is mainly achieved by increasing the sintering temperature of the rotary kiln. Sand grinding is difficult, the sintering temperature is high, the discharge performance is poor, and the particle size grading is not ideal. Therefore, the discharge performance of the currently prepared high-density lithium iron phosphate will decrease after the compaction density is increased.
[0062] The present application provides an anhydrous ferric phosphate and a preparation method thereof, a positive electrode material and a preparation method thereof, a positive electrode sheet, and a secondary battery. The anhydrous ferric phosphate has a suitable particle size grading, can achieve close stacking, and can further be used as a key raw material for preparing a positive electrode material to improve its compaction density and charging and discharging performance.
[0063] In order to solve the technical problem that the particle size distribution of anhydrous iron phosphate is poor, which leads to the inability of lithium iron phosphate positive electrode materials to have both high compaction density and high charge and discharge efficiency, the present application provides an anhydrous iron phosphate and a preparation method thereof, a positive electrode material and a preparation method thereof, a positive electrode sheet, and a secondary battery, wherein the anhydrous iron phosphate is tightly packed by controlling the anhydrous iron phosphate to have a suitable particle size distribution, and is further used as a key raw material for preparing the positive electrode material, thereby improving the compaction density and charge and discharge performance of the positive electrode material, thereby improving the compaction density and charge and discharge performance of the positive electrode sheet and the secondary battery.
[0064] In the first aspect, an embodiment of the present application provides an anhydrous ferric phosphate. In the primary particles of the anhydrous ferric phosphate, the number of particles with a particle size greater than or equal to 0.01 μm and less than 0.1 μm accounts for 10% to 30% by weight, the number of particles with a particle size of 0.1 μm to 0.2 μm accounts for 50% to 60%, the number of particles with a particle size greater than 0.2 μm and less than 0.4 μm accounts for 15% to 30%, and the number of particles with a particle size of 0.4 μm to 0.6 μm accounts for 0.2% to 10%.
[0065] Preferably, by weight percentage, among the primary particles of anhydrous ferric phosphate, the number of particles with a particle size greater than or equal to 0.01 μm and less than 0.1 μm accounts for 13.27% to 22.45%, the number of particles with a particle size of 0.1 μm to 0.2 μm accounts for 54.23% to 59.37%, the number of particles with a particle size greater than 0.2 μm and less than 0.4 μm accounts for 17.98% to 26.76%, and the number of particles with a particle size of 0.4 μm to 0.6 μm accounts for 0.3% to 7.46%.
[0066] More preferably, in the primary particles of anhydrous ferric phosphate, by weight percentage, the number of particles with a particle size greater than or equal to 0.01 μm and less than 0.1 μm accounts for 15.04% to 21.03%, the number of particles with a particle size of 0.1 μm to 0.2 μm accounts for 54.73% to 59.37%, the number of particles with a particle size greater than 0.2 μm and less than 0.4 μm accounts for 17.98% to 25.76%, and the number of particles with a particle size of 0.4 μm to 0.6 μm accounts for 1.49% to 6.68%.
[0067] Typically but not limiting, in terms of weight percentage, in the primary particles of anhydrous ferric phosphate, the number of particles with a particle size greater than or equal to 0.01 μm and less than 0.1 μm accounts for 10%, 15%, 20%, 25%, 30% or a range consisting of any two of them, the number of particles with a particle size of 0.1 μm to 0.2 μm accounts for 50%, 52%, 55%, 58%, 60% or a range consisting of any two of them, the number of particles with a particle size greater than 0.2 μm and less than 0.4 μm accounts for 15%, 18%, 20%, 22%, 25%, 28%, 30% or a range consisting of any two of them, and the number of particles with a particle size of 0.4 μm to 0.6 μm accounts for 0.2%, 1%, 2%, 5%, 8%, 10% or a range consisting of any two of them.
[0068] By controlling the particle size distribution within the above range, an anhydrous iron phosphate with good dispersibility is obtained, and its particle size distribution range is normally distributed. After sintering, the overall particle size will grow, but still maintain a good particle size distribution, thereby ensuring that the proportion of large and small particles of anhydrous iron phosphate is moderate, while reducing the proportion of coarse particles, and obtaining high compaction density and high discharge performance through the dense packing of anhydrous iron phosphate particles. Anhydrous iron phosphate with large and small particle sizes becomes the basis for further preparation of lithium iron phosphate materials with high compaction density, ensuring that the prepared lithium iron phosphate grains grow normally under high doping conditions, and obtaining a positive electrode material with high compaction density, good rate performance, and high charging and discharging efficiency.
[0069] Furthermore, in some embodiments, the particle shape of the anhydrous ferric phosphate is quasi-spherical, and the sphericity is 0.84 to 0.98, preferably 0.96 to 0.98.
[0070] In some embodiments, the tap density of anhydrous ferric phosphate is 0.93 g / cm 3 ~1.13g / cm 3 , preferably 0.95 g / cm 3 ~1.06g / cm 3 .
[0071] In some embodiments, the compacted density is 1.57 g / cm 3 ~1.61g / cm 3 , preferably 1.58 g / cm 3 ~1.61g / cm 3 .
[0072] In some embodiments, the iron-phosphorus ratio is (0.957-0.970): 1, preferably (0.963-0.966): 1. The iron-phosphorus ratio is the ratio of the amount of iron to the amount of phosphorus in anhydrous ferric phosphate.
[0073] In some embodiments, the BET specific surface area of anhydrous ferric phosphate is 8 m 2 / g~10.8m 2 / g, preferably 8.65m 2 / g~9.37m 2 / g.
[0074] Typically but not limiting, the particle shape of anhydrous ferric phosphate is spherical, and the sphericity is 0.84, 0.85, 0.90, 0.95, 0.98 or a range consisting of any two of them; the tap density of anhydrous ferric phosphate is 0.93 g / cm 3 , 0.95g / cm 3 , 1.00g / cm 3 , 1.05g / cm 3 , 1.10g / cm 3 , 1.13g / cm 3 Or any two of its values in the range, compacted density is 1.57g / cm 3 , 1.58g / cm 3 , 1.59g / cm 3 , 1.60g / cm 3 , 1.61g / cm 3 or a range of values consisting of any two of them, the iron-phosphorus ratio is 0.957:1, 0.960:1, 0.965:1, 0.970:1 or a range of values consisting of any two of them, and the BET specific surface area of anhydrous iron phosphate is 8m 2 / g, 8.5m 2 / g, 9m 2 / g, 9.5m 2 / g, 10m 2 / g, 10.5m 2 / g, 10.8m 2 / g or a range of values consisting of any two of them.
[0075] In the technical solution of the embodiment of the present application, the anhydrous iron phosphate has a higher sphericity and a higher tap density, indicating that the particle packing density is good, the particle size distribution is reasonable, and the compaction density of lithium iron phosphate is relatively high. In the case of good particle grading, the grinding time in the preparation process of lithium iron phosphate is further reduced, and the energy consumption is further reduced and the efficiency is improved while ensuring the performance of lithium iron phosphate. A smaller iron-phosphorus ratio is also conducive to the production of surplus phosphate, further modifying the lithium iron phosphate, and improving its compaction density and charging and discharging efficiency.
[0076] In a second aspect, the present application provides a method for preparing anhydrous ferric phosphate, comprising:
[0077] The ferrous source is mixed with the first dispersant to obtain a first raw material solution; the first phosphorus source is mixed with the second dispersant to obtain a second raw material solution;
[0078] The first raw material liquid, the second raw material liquid and the first oxidant are mixed, and after a first reaction treatment, a first mixture is obtained;
[0079] Adding a second phosphorus source to the first mixture, performing a second reaction treatment, and then adding a second oxidant to obtain a second mixture;
[0080] Adjusting the pH value and temperature of the second mixture, and obtaining anhydrous ferric phosphate after a third reaction treatment;
[0081] The first dispersant includes a cationic monomer and a coupling agent, and the second dispersant includes an anionic monomer and a chain transfer agent.
[0082] The most important reaction in the process of preparing anhydrous ferric phosphate by coprecipitation is to control the iron-phosphorus ratio and the reaction process, followed by controlling the particle size and morphology. This application reduces the surface tension of the reaction solvent and increases the reaction rate through the surfactant-like effect of the polymer formed by the first dispersant and the second dispersant, and at the same time utilizes the dispersion and complexation of the polymer (such as: the adsorption and binding effect of the carboxyl group in the anion of the polymer and the ferrous ion) to regulate the crystal morphology, and combines the step-by-step feeding of the oxidant and the phosphorus source to regulate the reaction process and control the iron-phosphorus ratio, so that the anhydrous ferric phosphate prepared has higher sphericity and more reasonable particle grading. Under the condition of a low proportion of large particles, the compaction density is significantly improved, and the compaction density of lithium iron phosphate prepared by this anhydrous ferric phosphate is significantly increased, and the charge-discharge rate performance is better.
[0083] Specifically, the present application uses a coprecipitation method to prepare ferric phosphate, wherein iron ions and phosphate radicals are subjected to precipitation reaction in proportion, cationic monomers are organic substances with cations and carbon-carbon double bonds, and anionic monomers are organic substances with anions and carbon-carbon double bonds, and cationic monomers and anionic monomers undergo polymerization reaction to generate polymers under the action of oxidants and reductants (partial iron in the form of ferrous ions), and the polymers carry anionic groups and cationic groups. There are ion-active parts in the reaction process of ferric phosphate, so it is easy to adsorb polymers; the polymers are adsorbed on the surface of ferric phosphate particles to form an adsorption layer, which is convenient for spacing particles and playing a dispersing role; at the same time, the polymers are adsorbed on the surface of ferric phosphate particles through electrostatic action to occupy active sites, which also leads to the growth of ferric phosphate being restricted, thereby playing a role in inhibiting the growth of ferric phosphate crystals; in addition, the polymers are surfactant-like substances, which can reduce the surface tension of the solution, promote the spherical growth of ferric phosphate particles to achieve the effect of minimum surface energy, thereby controlling the reaction rate and particle morphology.
[0084] In summary, the present application controls the generation and growth of iron phosphate and realizes particle size grading by combining the complexation and dispersion of polymers formed by cationic monomers and anionic monomers through the step-by-step feeding of phosphorus sources, thereby preparing anhydrous iron phosphate with high sphericity, good dispersibility and good particle size grading.
[0085] When the anhydrous iron phosphate of the present application is used as the basic raw material to prepare the lithium iron phosphate positive electrode material, the anhydrous iron phosphate prepared by the aforementioned method has better dispersibility, higher crystallinity, and better particle size distribution, and the interlacing and barrier stratification effect of the polymer formed by the cationic monomer and the anionic monomer is also beneficial to improving the rinsing efficiency. Combined with the control of the crystallization and growth of lithium iron phosphate during the preparation process of lithium iron phosphate, it is beneficial to significantly reduce the formation of large-grained single crystals in high-density lithium iron phosphate, ensure the effective proportion of high-efficiency lithium iron phosphate, and give it excellent energy storage performance; at the same time, when the iron-phosphorus ratio of the aforementioned anhydrous iron phosphate is (0.957~0.970):1, the surplus phosphate can also modify the lithium iron phosphate, ensuring the normal growth of the lithium iron phosphate grains under high doping conditions, thereby preparing a positive electrode material with high compaction density, good rate performance, and high charging and discharging efficiency.
[0086] Further, in some embodiments, the cationic monomer includes dimethyldiallylammonium chloride and / or acryloyloxyethyltrimethylammonium chloride.
[0087] In some embodiments, when the cationic monomer includes dimethyldiallyl ammonium chloride and acryloyloxyethyltrimethylammonium chloride, the mass ratio of dimethyldiallyl ammonium chloride to acryloyloxyethyltrimethylammonium chloride is 1:(2.5-3.5).
[0088] Typically but not limiting, when the cationic monomer includes dimethyldiallylammonium chloride and acryloyloxyethyltrimethylammonium chloride, the mass ratio between the two is 1:2.5, 1:2.8, 1:3.0, 1:3.2, 1:3.5 or a range consisting of any two of them.
[0089] In some embodiments, the coupling agent includes vinyltrimethoxysilane and / or 3-(methacryloyloxy)propyltrimethoxysilane.
[0090] In some embodiments, the anionic monomer includes one or more of methacrylic acid, itaconic acid, and fumaric acid. When the anionic monomer includes methacrylic acid and itaconic acid, the mass ratio of methacrylic acid to itaconic acid is 1: (2.5-3.5). Alternatively, when the anionic monomer includes methacrylic acid and fumaric acid, the mass ratio of methacrylic acid to fumaric acid is 1: (2.5-3.5).
[0091] Typically but not limiting, when the anionic monomer includes methacrylic acid and itaconic acid, the mass ratio between the two is 1:2.5, 1:2.8, 1:3.0, 1:3.2, 1:3.5 or a range consisting of any two of them; when the anionic monomer includes methacrylic acid and fumaric acid, the mass ratio between the two is 1:2.5, 1:2.8, 1:3.0, 1:3.2, 1:3.5 or a range consisting of any two of them.
[0092] In some embodiments, the chain transfer agent includes sodium hypophosphite and / or isopropyl alcohol.
[0093] In some embodiments, the molar ratio of the cationic monomer to the coupling agent is 100:(20-35).
[0094] In some embodiments, the molar ratio of the anionic monomer to the chain transfer agent is 100:(10-15).
[0095] Typically but not limiting, the molar ratio of the cationic monomer to the coupling agent is 100:20, 100:28, 100:30, 100:32, 100:35 or a range consisting of any two of them; the molar ratio of the anionic monomer to the chain transfer agent is 100:10, 100:11, 100:12, 100:13, 100:14, 100:15 or a range consisting of any two of them.
[0096] In the technical scheme of the embodiment of the present application, the polymer formed by the cationic monomer in the first dispersant and the anionic monomer in the second dispersant is polymerized relatively quickly under the conditions of the redox reaction, and there is a problem that some polymers are coated and buried by the newly generated iron phosphate, causing the polymer to lose the surfactant-like effect. The polymers formed by anionic monomers of different structures and cationic monomers of different structures have different reactivity and reaction rates. Therefore, the anionic monomers select a variety of methacrylic acid, itaconic acid and fumaric acid, or the cationic monomers select dimethyldiallyl ammonium chloride and acryloyloxyethyl trimethyl ammonium chloride, which is conducive to making the polymers formed by the polymerization of anionic monomers and cationic monomers adsorbed on the surface of iron phosphate at different rates, thereby improving the one-time formation of the polymer and the problem of being coated and buried by the newly generated iron phosphate. Exemplarily, the carboxyl group in the anionic monomer is combined with cations such as ferrous ions and ferric ions, and the cations in the cationic monomer are combined with anions such as phosphate, adsorbed on the surface of the obtained iron phosphate to form a coating layer, thereby dispersing the iron phosphate particles, thereby improving the dispersion effect by electrostatic complexation.
[0097] Exemplarily, dimethyldiallylammonium chloride has two double bonds and four methyl groups. In the cationic monomer, the steric hindrance of the methyl group reduces the electrostatic interaction between the cation of the cationic monomer and the free phosphate ion, slows down the rate at which the polymer is adsorbed and buried, is beneficial to improving the dispersion effect, and ensures the proportion of cations in the polymer; the three methyl groups in acryloyloxyethyltrimethylammonium chloride also provide steric hindrance and promote dispersion. After the chloride ions are dissolved, the ammonium ions in the residual structure are positively charged, and there is an electrostatic repulsion between the ferrous ions, ferric ions, and other ammonium ions, which is beneficial to retain the ammonium ions and thus facilitate their long-term dispersion effect; the combination of the above two is beneficial to improving the long-term dispersibility of the cations, controlling the polymerization efficiency, ensuring the full polymerization reaction between the anionic monomer and the cationic monomer, and controlling the molecular weight of the polymer, improving the problem that the polymer formed by the anionic monomer and the cationic monomer is coated and buried by the newly generated iron phosphate in the first mixture and / or the second mixture, thereby having a good dispersion effect on the iron phosphate particles, maintaining the long-term stability of the iron phosphate particles, and further promoting the uniform growth of the iron phosphate particles.
[0098] Exemplarily, methacrylic acid has a strong reaction activity, and when the concentration is high, it will react rapidly with cationic monomers to generate polymers with excessive molecular weight, resulting in failure to exert an inhibitory effect. The inhibitory effect mainly refers to the inhibitory effect that the anions in the polymer prevent the crystal nucleus from continuing to grow after the polymer is adsorbed on the surface of the iron phosphate crystal nucleus, and when the polymer molecular weight is too large, it is easy to disperse the iron phosphate particles and make it easier to grow, resulting in a weakened inhibitory effect of the polymer. Itaconic acid and fumaric acid are both dibasic acids, and the rate of polymerization with cationic monomers is relatively slow. Therefore, when itaconic acid or fumaric acid is used in conjunction with methacrylic acid, it is beneficial to control the reaction rate of anionic monomers and cationic monomers to form polymers and regulate the polymer molecular structure. At the same time, the strong complexation (based on the electrostatic adsorption of surface energy) between the carboxyl anions of methacrylic acid and the ferrous ions and ferric ions on the surface of the iron phosphate crystal nucleus will cause its carboxyl anions to be absorbed and consumed too quickly, and itaconic acid or fumaric acid slowly releases anions that are conducive to the continuous function of complexation, and the surfactant-like surfactant formed by combining the above-mentioned cationic monomers and anionic monomers reduces the surface tension of the solution, and the structure of the iron phosphate precursor is controlled to be spherical.
[0099] The above-mentioned cationic monomer and anionic monomer are more conducive to the smooth polymerization to form a polymer with the assistance of a coupling agent and a chain transfer agent. The polymer is a surfactant-like. First, the polymer plays a role in dispersing ions. Specifically, after the first mixture is mixed with the second mixture, some free ferrous ions, ferric ions and phosphate ions are combined with the carboxyl and amino groups in the cationic monomer and the anionic monomer through electrostatic action, which is conducive to the uniform distribution of free ferrous ions and ferric ions, and is easier to combine with the polymerization of the anionic monomer and the cationic monomer, so as to facilitate the control of the primary particle size of the generated iron phosphate particles. Subsequently, the polymer formed by the cationic monomer and the anionic monomer continues to disperse the crystal particles of iron phosphate. At the same time, the polymer formed by the anionic monomer and the cationic monomer further reduces the surface tension of the solution, thereby better promoting the spherical growth of the iron phosphate crystals, and improving the crystallinity of the iron phosphate crystals, which is conducive to improving the tap density and other properties of the finally obtained anhydrous iron phosphate.
[0100] Further, in some embodiments, the molar ratio of the iron element in the ferrous source to the first dispersant is 1:(0.0125-0.0150).
[0101] In some embodiments, the molar ratio of the iron element in the ferrous source to the phosphorus element in the phosphorus source is 1:(0.9-1.1).
[0102] Typically but not limiting, the molar ratio of the iron element in the ferrous source to the first dispersant is 1:0.0125, 1:0.0130, 1:0.0135, 1:0.0140, 1:0.0145, 1:0.0150 or a range consisting of any two of them; the molar ratio of the iron element in the ferrous source to the phosphorus element in the phosphorus source is 1:0.9, 1:0.95, 1:1.0, 1:1.05, 1:1.1 or a range consisting of any two of them.
[0103] In some embodiments, the molar ratio of phosphorus in the phosphorus source to the second dispersant is 1:(0.0150-0.0170).
[0104] Typically but not limiting, the molar ratio of phosphorus in the phosphorus source to the second dispersant is 1:0.0150, 1:0.0155, 1:0.0160, 1:0.0165, 1:0.0170 or a range consisting of any two of them.
[0105] In some embodiments, the ferrous source is prepared by the following method: mixing a titanium dioxide byproduct having ferrous sulfate with water, heating to dissolve, adding 5% to 15% ammonia water by mass for precipitation, filtering and retaining the filtrate to obtain a ferrous source.
[0106] In some embodiments, the first phosphorus source and the second phosphorus source are independently prepared by the following method: dissolving monoammonium phosphate, phosphoric acid and water and filtering, and adding 5% to 15% ammonia water by mass to the filtrate to adjust the pH value to 6 to 8.
[0107] In the technical solution of the embodiment of the present application, iron ions are formed by oxidation of ferrous ions using the first oxidant and / or the second oxidant, and the conversion rate of the reaction is affected by factors such as reactant concentration, temperature, and surface tension, so the iron-phosphorus ratio of the obtained anhydrous ferric phosphate is less than 1. Under the above-mentioned ratio conditions, it is more conducive to using excess phosphate to completely precipitate the iron ions, and further enhance the binding force between the positive charge of the cationic group from the cationic monomer in the polymer formed by the anionic monomer and the cationic monomer and the phosphate, as well as the binding force between the anionic group from the anionic monomer and the iron ion in the polymer formed by the anionic monomer and the cationic monomer, promote the spherical growth of particles, and play a better role in particle size regulation.
[0108] Furthermore, in some embodiments, the first oxidant includes hydrogen peroxide and / or sodium peroxide; preferably, the first oxidant is added in the form of a first oxidant solution, and the mass fraction of the first oxidant in the first oxidant solution is 20% to 30%.
[0109] In some embodiments, the second oxidant includes hydrogen peroxide and / or sodium peroxide; preferably, the second oxidant is added in the form of a second oxidant solution, and the mass fraction of the second oxidant in the second oxidant solution is 20% to 30%.
[0110] In some embodiments, the mass ratio of the first phosphorus source to the second phosphorus source is (15-25):(75-85).
[0111] Typically but not limitatively, the mass ratio of the first phosphorus source to the second phosphorus source is 15:85, 18:82, 20:80, 22:78, 25:75 or a range consisting of any two of them.
[0112] In some embodiments, the molar ratio of the first oxidant to the iron element in the ferrous source is (0.6-1.1):1, and the molar ratio of the second oxidant to the iron element in the ferrous source is (2.1-2.8):1.
[0113] Typically but not limiting, the molar ratio of the iron element in the ferrous source to the first oxidant is 1:0.6, 1:0.7, 1:0.8, 1:0.9, 1:1.0, 1:1.1 or a range consisting of any two of them; the molar ratio of the iron element in the ferrous source to the second oxidant is 1:2.1, 1:2.2, 1:2.5, 1:2.6, 1:2.8 or a range consisting of any two of them.
[0114] In the technical scheme of the embodiment of the present application, the concentration of iron ions is controlled by the first oxidant and / or the second oxidant, and the concentration of phosphate is controlled by the addition of the phosphorus source, and the reaction rate is controlled from two aspects. The faster the reaction rate, the more crystal nuclei are generated and the smaller the crystal size; the slower the reaction, the larger the crystal size, thereby controlling the particle size of the iron phosphate crystal. The above-mentioned oxidant can be used together with the concentration of the reactants to regulate the reaction rate within a more suitable degree; the addition amount of the first phosphorus source and the second phosphorus source is controlled to control the step-by-step feeding, thereby controlling the generation and growth of iron phosphate, further improving the particle size gradation, and being conducive to further improving the sphericity, dispersibility and particle size gradation of anhydrous iron phosphate.
[0115] Further, in some embodiments, in the first reaction treatment, the temperature is 40°C to 60°C, and the time is 0.5h to 1h; and / or, in the second reaction treatment, the temperature is 40°C to 60°C, and the time is 5min to 10min.
[0116] Typically but not limiting, in the first reaction treatment, the temperature is 40°C, 45°C, 50°C, 55°C, 60°C or a range consisting of any two of them, and the time is 0.5h, 0.6h, 0.7h, 0.8h, 0.9h, 1h or a range consisting of any two of them.
[0117] Typically but not limiting, in the second reaction treatment, the temperature is 40°C, 45°C, 50°C, 55°C, 60°C or a range consisting of any two of them, and the time is 5 min, 6 min, 7 min, 8 min, 9 min, 10 min or a range consisting of any two of them.
[0118] In the technical solution of the embodiment of the present application, the control of the above-mentioned reaction temperature and time can control the precipitation rate and dispersion effect of iron phosphate by promoting the polymerization rate and degree of cationic monomers and anionic monomers, and further improve the particle size distribution of anhydrous iron phosphate particles.
[0119] Further, in some embodiments, the step of adjusting the pH value and temperature of the second mixture, and obtaining anhydrous iron phosphate after the third reaction treatment includes: adjusting the temperature of the second mixture to 40°C to 60°C, controlling the pH value of the second mixture to 0.9 to 1.5, heating to 90°C to 95°C to react to a pH value of 1.6 to 2.0 to obtain a third mixture; and sequentially filtering, rinsing, flash evaporating, drying, crushing, and sieving the third mixture to obtain anhydrous iron phosphate. Preferably, heating to 90°C to 95°C to react for 1.5h to 2.5h to a pH value of 1.6 to 2.0 to obtain the third mixture is conducive to fully reacting the materials.
[0120] Typically but not limiting, the temperature of the second mixture is adjusted to 40°C, 45°C, 50°C, 55°C, 60°C or a range consisting of any two of them, the pH of the second mixture is controlled to 0.9-1.5, the temperature is raised to 90°C-95°C and reacted to a pH of 1.6-2.0 to obtain a third mixture.
[0121] In the technical solution of the embodiment of the present application, by adjusting the temperature and pH value of the second mixture within an appropriate range, the stable precipitation of iron phosphate can be further controlled, and combined with pressure filtration, rinsing, flash evaporation, drying, crushing and screening, anhydrous iron phosphate with high sphericity, good dispersibility and good particle size grading as described above can be prepared, making the preparation method more practical.
[0122] In some embodiments, the pH value of the second mixture is obtained by testing a solution portion of the second mixture.
[0123] In a third aspect, the present invention provides a positive electrode material, the general formula of which is LiFe 1-a-b- c Y a Ce b M c PO4@C, wherein M is one or more of tin, titanium, boron, and manganese, a is 0.007 to 0.013, b is 0.029 to 0.057, and c is 0.01 to 0.033; the mass fraction of C in the positive electrode material is 1.2% to 1.4%.
[0124] Typically, but not limiting, the general formula of the positive electrode material is LiFe 1-a-b-c Y a Ce b M c PO4@C, a is 0.007, 0.008, 0.009, 0.010, 0.011, 0.012, 0.013 or a range consisting of any two of them, b is 0.029, 0.030, 0.035, 0.040, 0.045, 0.050, 0.055, 0.057 or a range consisting of any two of them, c is 0.016, 0.020, 0.025, 0.030, 0.033 or a range consisting of any two of them; the mass percentage of C in the positive electrode material is 1.2%, 1.25%, 1.3%, 1.35%, 1.4% or a range consisting of any two of them.
[0125] In some embodiments, a is preferably 0.008 to 0.012, b is preferably 0.03 to 0.052, and c is preferably 0.01 to 0.026.
[0126] In some embodiments, the mass fraction of C in the positive electrode material is preferably 1.28% to 1.34%.
[0127] In some embodiments, the chemical formula of the positive electrode material can be expressed as: LiFe 0.912 Y 0.012 Sn 0.024 Ce 0.052 PO4@C、LiFe 0.910 Y 0.012 Ti 0.026 Ce 0.052 PO4@C、LiFe 0.94 Y 0.012 Ti 0.018 Ce 0.05 PO4@C、LiFe 0.943 Y 0.008 Ti 0.016 Ce 0.033 PO4@C、LiFe 0.936 Y 0.01 Mn 0.018 Ce 0.036 PO4@C、LiFe 0.94 Y 0.01 Ce 0.03 (PO4) 0.99 (BO3) 0.01 At least one of @C.
[0128] In the technical scheme of the embodiment of the present application, anhydrous iron phosphate with good particle size distribution (the anhydrous iron phosphate can be anhydrous iron phosphate as described above or anhydrous iron phosphate prepared by the preparation method of anhydrous iron phosphate as described above) is used as a key synthetic raw material. Due to its reasonable particle size distribution, high tap density, high compaction density, and good particle packing density, the compaction density of the lithium iron phosphate finally prepared is also relatively high. At the same time, three metal cations with different action mechanisms and doping ratios are combined for doping modification, among which Y doping can inhibit particle growth and avoid excessive particle growth leading to poor electrical performance; Ce has a high valence, and lithium ion conductivity can be significantly improved after doping; M (tin, titanium, boron, manganese) has a valence close to Fe, which is conducive to further improving the stability of the positive electrode material after doping. At the same time, the above-mentioned metal cations can combine with phosphate in anhydrous iron phosphate to reduce the coarsening of phosphate grains, thereby ensuring the stability of the initial structure of iron phosphate and the normal growth of the grains of the positive electrode material under the condition of high metal element doping, so that the positive electrode material has the advantages of high compaction density, good rate performance, and high charging and discharging efficiency.
[0129] Furthermore, in some embodiments, the average primary particle size of the positive electrode material is 0.24 μm to 0.34 μm; wherein, in the positive electrode material, the number fraction of particles with an average primary particle size greater than or equal to 1 μm is less than or equal to 3.20%, and the compaction density is 2.52 g / cm 3 ~2.64g / cm 3 . Preferably, in the positive electrode material, the number fraction of primary particles with a particle size of less than or equal to 200 nm is 32 to 67%. Preferably, the number fraction of particles with an average primary particle size of greater than or equal to 1 μm in the positive electrode material is 0% to 3.12%; more preferably, the number fraction of particles with an average primary particle size of greater than or equal to 1 μm in the positive electrode material is 0.93% to 3.12%.
[0130] Typically but not limiting, the average primary particle size of the positive electrode material is 0.24 μm, 0.25 μm, 0.028 μm, 0.30 μm, 0.32 μm, 0.34 μm or a range consisting of any two of these values.
[0131] A typical but non-limiting example is that the compacted density of the cathode material is 2.52 g / cm 3 , 2.55g / cm 3 , 2.58g / cm 3 , 2.60g / cm 3 , 2.62g / cm 3 , 2.64g / cm 3 Or a range of values consisting of any two of them.
[0132] In the technical scheme of the embodiment of the present application, the principle of lithium iron phosphate charging and discharging is that lithium ions are embedded and removed under the action of voltage. The larger the lithium iron phosphate particles are, the more difficult it is for lithium ions to be removed and embedded, resulting in reduced charging and discharging performance. Spherical particles are conducive to ensuring the shortest lithium ion movement path, reducing the obstacles to lithium ion embedding and removal, and effectively improving charging and discharging performance. The raw material of the above-mentioned positive electrode material of the present application is anhydrous iron phosphate with large and small particle sizes, which is conducive to controlling the crystallization and growth process of lithium iron phosphate, further reducing the generation of large particle single crystals in lithium iron phosphate, so that the positive electrode material has excellent compaction density and energy storage performance.
[0133] In a fourth aspect, an embodiment of the present application provides a method for preparing a positive electrode material, comprising the following steps:
[0134] The anhydrous ferric phosphate, lithium source, carbon source, complexing agent, dopant and water are mixed to obtain a mixed material;
[0135] The mixed material is sintered under a protective atmosphere to obtain a positive electrode material;
[0136] The dopants include yttrium oxide, cerium oxide and other oxides, and the other oxides include one or more of tin oxide, titanium oxide, boron oxide and manganese oxide.
[0137] In the technical solution of the embodiment of the present application, the higher the sphericity of the anhydrous iron phosphate particles used, the more the particle size distribution tends to be normally distributed, the higher the packing density, and the higher the compaction density. The process of preparing lithium iron phosphate is mainly to embed lithium ions and doping elements into iron phosphate through sintering treatment. The iron phosphate particles will also grow under high temperature conditions, so the morphology and particle distribution of anhydrous iron phosphate directly determine the particle morphology and particle size distribution of lithium iron phosphate.
[0138] The present application uses anhydrous iron phosphate with high crystallinity, low impurity content, excellent particle size grading, high sphericity, high bulk density and high compaction density (the anhydrous iron phosphate can be the anhydrous iron phosphate as described above or the anhydrous iron phosphate prepared by the preparation method of anhydrous iron phosphate as described above) as a raw material, and then controls the crystallization and growth process of lithium iron phosphate, which significantly reduces the formation of large-particle single crystals in high-density lithium iron phosphate. During the crystallization and growth of lithium iron phosphate, the chelating agent plays an inhibitory role before carbon coating, effectively avoiding the formation of crystal nuclei and reducing the generation of invalid single crystals during the growth of lithium iron phosphate particles. On the one hand, the effective proportion of high-efficiency lithium iron phosphate is guaranteed and the compaction density is improved; on the other hand, the good carbon coating effect and low powder internal resistance of lithium iron phosphate are guaranteed, and polarization is reduced, thereby exerting excellent charging and discharging performance and long-lasting cycle performance.
[0139] Further, in some embodiments, the complexing agent includes glycerol and / or sodium gluconate; and / or, the dopant includes yttrium oxide, cerium oxide and other oxides, and the other oxides include one or more of tin dioxide, titanium dioxide, boron trioxide and manganese carbonate; preferably, the mass ratio of yttrium oxide, cerium oxide and other oxides is 1:(2-3):(1-2); and / or, the mass ratio of anhydrous ferric phosphate to the complexing agent is 1:(0.02-0.03); and / or, the mass ratio of anhydrous ferric phosphate to the dopant is 1:(0.008-0.009); and / or, the mass ratio of anhydrous ferric phosphate to the lithium source is 1:(1-1.05); and / or, the mass ratio of anhydrous ferric phosphate to the carbon source is 1:(0.09-0.11).
[0140] Typically but not limiting, the mass ratio of yttrium oxide to cerium oxide is 1:2, 1:2.2, 1:2.5, 1:2.8, 1:3 or a range consisting of any two of them; the mass ratio of yttrium oxide to other oxide-containing materials is 1:1, 1:1.2, 1:1.5, 1:1.8, 1:2 or a range consisting of any two of them.
[0141] Typically but not limiting, the mass ratio of anhydrous ferric phosphate to the complexing agent is 1:0.02, 1:0.022, 1:0.025, 1:0.028, 1:0.03 or a range consisting of any two of them.
[0142] Typically but not limiting, the mass ratio of anhydrous ferric phosphate to the dopant is 1:0.008, 1:0.0082, 1:0.0085, 1:0.0088, 1:0.009 or a range consisting of any two of them.
[0143] Typically, but not limiting, the molar ratio of anhydrous ferric phosphate to lithium source is 1:1, 1:1.01, 1:1.02, 1:1.03, 1:1.04, 1:1.05 or a range consisting of any two of them.
[0144] Typically but not limiting, the mass ratio of anhydrous ferric phosphate to carbon source is 1:0.09, 1:0.095, 1:0.10, 1:0.105, 1:0.11 or a range consisting of any two of them.
[0145] In the technical solution of the embodiment of the present application, the complexing agent is glycerol or sodium gluconate, which combines with the active sites of the raw materials through strong polarity during the sintering process, inhibits the formation of crystal nuclei, reduces the generation of lithium iron phosphate single crystals, and improves the purity of lithium iron phosphate, thereby improving the electrical properties of the positive electrode material. By controlling the raw material ratio within the above range, the synthesis of lithium iron phosphate is more complete, thereby reducing the waste of raw materials, and further reducing the preparation cost while maintaining the excellent electrical properties of the positive electrode material.
[0146] Further, in some embodiments, the step of obtaining the positive electrode material after sintering the mixed material under a protective atmosphere includes: grinding the mixed material to obtain a ground material, and the D50 particle size of the ground material is 0.38μm~0.42μm; spray drying the ground material to obtain a spray material, and the D50 particle size of the spray material is 3.4μm~6.7μm; sintering the spray material under a protective atmosphere to obtain the positive electrode material; preferably, the sintering temperature is 760℃~820℃, and the time is 10h~18h.
[0147] Typically but not limiting, the D50 particle size of the ground material is 0.38 μm, 0.39 μm, 0.40 μm, 0.41 μm, 0.42 μm or a range consisting of any two of them; the D50 particle size of the spray material is 3.4 μm, 3.5 μm, 4.0 μm, 4.5 μm, 5.0 μm, 5.5 μm, 6.0 μm, 6.5 μm, 6.7 μm or a range consisting of any two of them.
[0148] Typically but not limiting, the sintering temperature is 760°C, 770°C, 780°C, 790°C, 800°C, 810°C, 820°C or a range consisting of any two of them, and the sintering time is 10h, 12h, 15h, 16h, 18h or a range consisting of any two of them.
[0149] In some embodiments, the protective atmosphere is achieved by a protective gas, which can be selected from at least one of nitrogen and argon.
[0150] In the technical solution of the embodiment of the present application, the anhydrous iron phosphate has high sphericity, good particle gradation, and small particle size of the product after grinding and spray drying, which is conducive to further reducing the grinding and spray drying time, and further reducing production energy consumption and improving production efficiency under the premise of ensuring the particle size and performance of the obtained lithium iron phosphate. By controlling the sintering temperature within an appropriate range, on the one hand, the compaction density is increased and the lithium ion diffusion rate is increased, and on the other hand, the proportion of single crystal lithium iron phosphate is smaller, the polarization is smaller, and the electrochemical performance of the positive electrode material is better.
[0151] In a fifth aspect, an embodiment of the present application provides a positive electrode plate, comprising a positive electrode current collector and a positive electrode active layer disposed on at least one side of the positive electrode current collector, wherein the positive electrode active layer comprises the above-mentioned positive electrode material.
[0152] In this embodiment, the positive electrode plate includes the above-mentioned positive electrode material, and thus has the advantages of good rate performance and high charging and discharging efficiency.
[0153] In a sixth aspect, an embodiment of the present application provides a secondary battery, comprising the above-mentioned positive electrode plate.
[0154] In this embodiment, the secondary battery includes the above-mentioned positive electrode plate, and thus has the advantages of good rate performance and high charging and discharging efficiency.
[0155] Some specific embodiments are listed below. It should be noted that the embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If specific techniques or conditions are not specified in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. The reagents or instruments used without specifying the manufacturer are all conventional products that can be obtained commercially.
[0156] 1. Preparation method
[0157] Example 1
[0158] This embodiment provides a method for preparing anhydrous iron phosphate and a positive electrode material, and the specific steps of the preparation method are as follows:
[0159] Step 1: 1) mixing the titanium dioxide byproduct with ferrous sulfate with water, heating and dissolving, adding 5% ammonia water for precipitation, filtering and removing impurities, and obtaining a ferrous solution with a ferrous ion mass fraction of 1.5 mol / L and a pH value of 2.8;
[0160] 2) Preparation of phosphorus source: industrial monoammonium phosphate is dissolved in phosphoric acid and water, filtered, and then 5% ammonia water is added to adjust the pH value to neutral to obtain a phosphorus source solution, wherein PO4 3- The content is 2mol / L;
[0161] 3) Preparation of dispersant: 0.010 mol of dimethyldiallylammonium chloride and 0.0028 mol of vinyltrimethoxysilane were mixed to form liquid A, and 0.015 mol of methacrylic acid and 0.0015 mol of isopropanol were mixed to form liquid B, and the mixture was stirred evenly;
[0162] 4) Based on 1 mol of iron (i.e., based on a solution containing 1 mol of ferrous ions, the same applies hereinafter), firstly, a ferrous source and a solution A are mixed and added to the reactor as a base material, and then 1 mol of a phosphorus source solution (i.e., a solution containing 1 mol of PO4 3- The phosphorus source solution (hereinafter the same) is mixed with 15% of solution B, and 20% of 3.2 mol of hydrogen peroxide solution is slowly added dropwise to carry out a synthesis reaction. After the addition is completed, the mixture is stirred at 50° C. for half an hour, and then the remaining phosphorus source is added at once. After stirring at 50° C. for 5 minutes, the remaining hydrogen peroxide solution is slowly added dropwise, and the reaction temperature is kept at no more than 60° C. After the addition is completed, the pH value is adjusted to 1.2 with phosphoric acid, and then the temperature is raised to 95° C. and the reaction is continued with stirring for 2 hours until the pH value is 1.8, and filter pressing, rinsing, flash evaporation, drying, crushing, and sieving are performed to obtain anhydrous ferric phosphate.
[0163] Step 2: The anhydrous iron phosphate prepared in step 1, 1.02 times the amount of lithium carbonate of the anhydrous iron phosphate substance, 0.86% of the mass of the anhydrous iron phosphate, yttrium oxide, tin dioxide and cerium oxide in a mass ratio of 1:2:3, and 11.8% of the mass of the anhydrous iron phosphate in a mass ratio of 1:4 of propylene glycol and soluble starch, are added with pure water and stirred to form a slurry with a solid content of 48.0%, and the D50 particle size is adjusted to 0.38 μm by sand milling, and then spray-dried at a temperature above 215°C to control the D50 particle size to 3.4 μm; then heated to 786°C at 5°C / min in a nitrogen protective atmosphere, kept warm for 12 hours, cooled to below 100°C by air cooling, and crushed to obtain a lithium iron phosphate positive electrode material.
[0164] Example 2
[0165] This embodiment provides a method for preparing anhydrous iron phosphate and a positive electrode material, and the specific steps of the preparation method are as follows:
[0166] Step 1: 1) mixing the titanium dioxide byproduct with ferrous sulfate with water, heating and dissolving, adding 5% ammonia water for precipitation, filtering and removing impurities, and obtaining a ferrous solution with a ferrous ion mass fraction of 2 mol / L and a pH value of 3.2;
[0167] 2) Preparation of phosphorus source: industrial monoammonium phosphate is dissolved in phosphoric acid and water, filtered, and then 5% ammonia water is added to adjust the pH value to neutral to obtain a phosphorus source solution, wherein PO4 3- The content is 2mol / L;
[0168] 3) Dispersant preparation: 0.012 mol of dimethyldiallylammonium chloride, acryloyloxyethyltrimethylammonium chloride and 0.0028 mol of 3-(methacryloyloxy)propyltrimethoxysilane in a mass ratio of 1:3 were mixed to form liquid A; 0.015 mol of methacrylic acid, fumaric acid and 0.0019 mol of sodium hypophosphite in a mass ratio of 1:3 were mixed to form liquid B; and the mixture was stirred evenly;
[0169] 4) Based on 1 mol of iron, firstly, a ferrous source and liquid A are mixed and added into a reactor as a base material, then 20% of 1 mol of phosphorus source solution and liquid B are mixed, and 20% of 3.2 mol of hydrogen peroxide solution are slowly added dropwise to carry out a synthesis reaction, and after the addition is completed, the reaction is stirred at 50° C. for half an hour, and then the remaining phosphorus source is added at once, and the stirring is continued at 50° C. for 5 minutes, and then the remaining hydrogen peroxide solution is slowly added dropwise, and the reaction temperature is kept not higher than 60° C. After the addition is completed, the pH value is adjusted to 1.2 with phosphoric acid, and then the temperature is raised to 95° C. and the stirring reaction is continued for 2 hours until the pH value is 1.8, and filter pressing, rinsing, flash evaporation, drying, crushing, and sieving are performed to obtain anhydrous ferric phosphate.
[0170] Step 2: The anhydrous iron phosphate prepared in step 1, 1.02 times the amount of lithium carbonate of the anhydrous iron phosphate substance, 0.86% of the mass of the anhydrous iron phosphate, yttrium oxide, tin dioxide and cerium oxide in a mass ratio of 1:2:3, and 11.8% of the mass of the anhydrous iron phosphate in a mass ratio of 1:4 of propylene glycol and soluble starch, are added with pure water and stirred to form a slurry with a solid content of 48.0%, and the D50 particle size is adjusted to 0.38 μm by sand milling, and then spray-dried at a temperature above 215°C to control the D50 particle size to 5 μm; then heated to 786°C at 5°C / min in a nitrogen protective atmosphere, kept warm for 12 hours, cooled to below 100°C by air cooling, and crushed to obtain a lithium iron phosphate positive electrode material.
[0171] Example 3
[0172] This embodiment provides a method for preparing anhydrous iron phosphate and a positive electrode material, and the specific steps of the preparation method are as follows:
[0173] Step 1: 1) mixing the titanium dioxide byproduct with ferrous sulfate with water, heating and dissolving, adding 5% ammonia water for precipitation, filtering and removing impurities, and obtaining a ferrous solution with a ferrous ion mass fraction of 2 mol / L and a pH value of 3.0;
[0174] 2) Preparation of phosphorus source: industrial monoammonium phosphate is dissolved in phosphoric acid and water, filtered, and then 5% ammonia water is added to adjust the pH value to neutral to obtain a phosphorus source solution, wherein PO4 3- The content is 2mol / L;
[0175] 3) Dispersant preparation: 0.01 mol of dimethyldiallylammonium chloride, acryloyloxyethyltrimethylammonium chloride and 0.0031 mol of vinyltrimethoxysilane in a mass ratio of 1:3 were mixed to form liquid A; 0.014 mol of methacrylic acid, itaconic acid and 0.0017 mol of sodium hypophosphite in a mass ratio of 1:3 were mixed to form liquid B; and the mixture was stirred evenly;
[0176] 4) Based on 1 mol of iron, firstly, a ferrous source and a liquid A are mixed and added into a reactor as a base material, then 25% of 1 mol of a phosphorus source solution and a liquid B are mixed, and 20% of a 3.4 mol hydrogen peroxide solution are slowly added dropwise to carry out a synthesis reaction, and after the addition is completed, the reaction is stirred at 50° C. for half an hour, and then the remaining phosphorus source is added at once, and the stirring is continued at 50° C. for 5 minutes, and then the remaining hydrogen peroxide solution is slowly added dropwise, and the reaction temperature is kept not higher than 60° C. After the addition is completed, the pH value is adjusted to 1.0 with phosphoric acid, and then the temperature is raised to 95° C. and the stirring reaction is continued for 2 hours until the pH value is 1.8. The obtained third mixture is subjected to filter pressing, rinsing, flash evaporation, drying, crushing, and sieving to obtain anhydrous ferric phosphate.
[0177] Step 2: The anhydrous iron phosphate prepared in step 1, 1.02 times the amount of lithium carbonate of the anhydrous iron phosphate substance, 0.86% of the mass of the anhydrous iron phosphate, yttrium oxide, tin dioxide and cerium oxide in a mass ratio of 1:2:3, and 11.8% of the mass of the anhydrous iron phosphate in a mass ratio of 1:4 of propylene glycol and soluble starch, are added with pure water and stirred to form a slurry with a solid content of 48.0%, and the D50 particle size is adjusted to 0.38 μm by sand milling, and then spray-dried at a temperature above 215°C to control the D50 particle size to 6.7 μm; then heated to 786°C at 5°C / min in a nitrogen protective atmosphere, kept warm for 12 hours, cooled to below 100°C by air cooling, and crushed to obtain a lithium iron phosphate positive electrode material.
[0178] Example 4
[0179] This embodiment provides a method for preparing anhydrous iron phosphate and a positive electrode material, and the specific steps of the preparation method are as follows:
[0180] Step 1: 1) mixing the titanium dioxide byproduct with ferrous sulfate with water, heating and dissolving, adding 5% ammonia water for precipitation, filtering and removing impurities, and obtaining a ferrous solution with a ferrous ion mass fraction of 2 mol / L and a pH value of 3.0;
[0181] 2) Preparation of phosphorus source: industrial monoammonium phosphate is dissolved in phosphoric acid and water, filtered, and then 5% ammonia water is added to adjust the pH value to neutral to obtain a phosphorus source solution, wherein PO4 3- The content is 2mol / L;
[0182] 3) Dispersant preparation: 0.01 mol of dimethyldiallylammonium chloride, acryloyloxyethyltrimethylammonium chloride and 0.0031 mol of vinyltrimethoxysilane in a mass ratio of 1:3 were mixed to form liquid A; 0.014 mol of methacrylic acid, itaconic acid and 0.0017 mol of sodium hypophosphite in a mass ratio of 1:3 were mixed to form liquid B; and the mixture was stirred evenly;
[0183] 4) Based on 1 mol of iron, firstly, a ferrous source and a liquid A are mixed and added to a reactor as a base material, and then 25% of 1 mol of a phosphorus source solution and a liquid B are mixed, and 20% of a 3.4 mol hydrogen peroxide solution are slowly added dropwise to carry out a synthesis reaction. After the addition is completed, the reaction is stirred at 50° C. for half an hour, and then the remaining phosphorus source is added at once. After stirring at 50° C. for 5 minutes, the remaining hydrogen peroxide solution is slowly added dropwise, and the reaction temperature is kept at no more than 60° C. After the addition is completed, the pH value is adjusted to 1.0 with phosphoric acid, and then the temperature is raised to 95° C. and the reaction is continued with stirring for 2 hours until the pH value is 1.8, and filter pressing, rinsing, flash evaporation, drying, crushing, and sieving are performed to obtain anhydrous ferric phosphate.
[0184] Step 2: The anhydrous iron phosphate prepared in step 1, 1.03 times the amount of lithium carbonate of the anhydrous iron phosphate substance, 0.86% of the mass of the anhydrous iron phosphate, yttrium oxide, titanium dioxide and cerium oxide in a mass ratio of 1:2:3, and 11.8% of the mass of the anhydrous iron phosphate in a mass ratio of 1:4 of propylene glycol and β-cyclodextrin, are added with pure water and stirred to form a slurry with a solid content of 48.0%, and the D50 particle size is adjusted to 0.40 μm by sand milling, and then spray-dried at a temperature above 215°C to control the D50 particle size to 6.7 μm; then heated to 786°C at 5°C / min in a nitrogen protective atmosphere, kept warm for 16 hours, cooled to below 100°C by air cooling, and crushed to obtain a lithium iron phosphate positive electrode material.
[0185] Example 5
[0186] This embodiment provides a method for preparing anhydrous iron phosphate and a positive electrode material, and the specific steps of the preparation method are as follows:
[0187] Step 1: 1) mixing the titanium dioxide byproduct with ferrous sulfate with water, heating and dissolving, adding 5% ammonia water for precipitation, filtering and removing impurities, and obtaining a ferrous solution with a ferrous ion mass fraction of 2 mol / L and a pH value of 3.0;
[0188] 2) Preparation of phosphorus source: industrial monoammonium phosphate is dissolved in phosphoric acid and water, filtered, and then 5% ammonia water is added to adjust the pH value to neutral to obtain a phosphorus source solution, wherein PO4 3- The content is 2mol / L;
[0189] 3) Dispersant preparation: 0.01 mol of dimethyldiallylammonium chloride, acryloyloxyethyltrimethylammonium chloride and 0.0031 mol of vinyltrimethoxysilane in a mass ratio of 1:3 were mixed to form liquid A; 0.014 mol of methacrylic acid, itaconic acid and 0.0017 mol of sodium hypophosphite in a mass ratio of 1:3 were mixed to form liquid B; and the mixture was stirred evenly;
[0190] 4) Based on 1 mol of iron, firstly, a ferrous source and a liquid A are mixed and added to a reactor as a base material, and then 25% of 1 mol of a phosphorus source solution and a liquid B are mixed, and 20% of a 3.4 mol hydrogen peroxide solution are slowly added dropwise to carry out a synthesis reaction. After the addition is completed, the reaction is stirred at 50° C. for half an hour, and then the remaining phosphorus source is added at once. After stirring at 50° C. for 5 minutes, the remaining hydrogen peroxide solution is slowly added dropwise, and the reaction temperature is kept at no more than 60° C. After the addition is completed, the pH value is adjusted to 1.0 with phosphoric acid, and then the temperature is raised to 95° C. and the reaction is continued with stirring for 2 hours until the pH value is 1.8, and filter pressing, rinsing, flash evaporation, drying, crushing, and sieving are performed to obtain anhydrous ferric phosphate.
[0191] Step 2: The anhydrous iron phosphate prepared in step 1, 1.03 times the amount of lithium carbonate of the anhydrous iron phosphate substance, 0.83% of the mass of the anhydrous iron phosphate, yttrium oxide, titanium dioxide and cerium oxide in a mass ratio of 2:3:5, and 12.7% of the mass of the anhydrous iron phosphate in a mass ratio of 1:4 of propylene glycol and β-cyclodextrin, are added with pure water and stirred to form a slurry with a solid content of 48.0%, and the D50 particle size is adjusted to 0.42 μm by sand milling, and then spray-dried at a temperature above 215°C to control the D50 particle size to 4.5 μm; then heated to 788°C at 5°C / min in a nitrogen protective atmosphere, kept warm for 14 hours, cooled to below 100°C by air cooling, and crushed to obtain a lithium iron phosphate positive electrode material.
[0192] Example 6
[0193] This embodiment provides a method for preparing anhydrous iron phosphate and a positive electrode material, and the specific steps of the preparation method are as follows:
[0194] Step 1: 1) mixing the titanium dioxide byproduct with ferrous sulfate with water, heating and dissolving, adding 5% ammonia water for precipitation, filtering and removing impurities, and obtaining a ferrous solution with a ferrous ion mass fraction of 2 mol / L and a pH value of 3.0;
[0195] 2) Preparation of phosphorus source: industrial monoammonium phosphate is dissolved in phosphoric acid and water, filtered, and then 5% ammonia water is added to adjust the pH value to neutral to obtain a phosphorus source solution, wherein PO4 3- The content is 2mol / L;
[0196] 3) Dispersant preparation: 0.01 mol of dimethyldiallylammonium chloride, acryloyloxyethyltrimethylammonium chloride and 0.0031 mol of vinyltrimethoxysilane in a mass ratio of 1:3 were mixed to form liquid A; 0.014 mol of methacrylic acid, itaconic acid and 0.0017 mol of sodium hypophosphite in a mass ratio of 1:3 were mixed to form liquid B; and the mixture was stirred evenly;
[0197] 4) Based on 1 mol of iron, firstly, a ferrous source and a liquid A are mixed and added to a reactor as a base material, and then 25% of 1 mol of a phosphorus source solution and a liquid B are mixed, and 20% of a 3.4 mol hydrogen peroxide solution are slowly added dropwise to carry out a synthesis reaction. After the addition is completed, the reaction is stirred at 50° C. for half an hour, and then the remaining phosphorus source is added at once. After stirring at 50° C. for 5 minutes, the remaining hydrogen peroxide solution is slowly added dropwise, and the reaction temperature is kept at no more than 60° C. After the addition is completed, the pH value is adjusted to 1.0 with phosphoric acid, and then the temperature is raised to 95° C. and the reaction is continued with stirring for 2 hours until the pH value is 1.8, and filter pressing, rinsing, flash evaporation, drying, crushing, and sieving are performed to obtain anhydrous ferric phosphate.
[0198] Step 2: The anhydrous iron phosphate prepared in step 1, 1.03 times the amount of lithium carbonate of the anhydrous iron phosphate substance, 0.83% of the mass of the anhydrous iron phosphate, yttrium oxide, titanium dioxide and cerium oxide in a mass ratio of 2:3:5, and 13.2% of the mass of the anhydrous iron phosphate in a mass ratio of 1:4 of propylene glycol and β-cyclodextrin, are added with pure water and stirred to form a slurry with a solid content of 48.0%, and the D50 particle size is adjusted to 0.40 μm by sand milling, and then spray-dried at a temperature above 215°C to control the D50 particle size to 4.5 μm; then heated to 790°C at 5°C / min in a nitrogen protective atmosphere, kept warm for 14 hours, cooled to below 100°C by air cooling, and crushed to obtain a lithium iron phosphate positive electrode material.
[0199] Example 7
[0200] The difference from Example 5 is that, in step 1: 3) dispersant preparation, 0.0105 mol of dimethyldiallylammonium chloride, acryloyloxyethyltrimethylammonium chloride and 0.0021 mol of 3-(methacryloyloxy)propyltrimethoxysilane in a mass ratio of 1:2.5 are mixed to form liquid A, 0.014 mol of methacrylic acid, itaconic acid and 0.0014 mol of sodium hypophosphite in a mass ratio of 1:2.5 are mixed to form liquid B, and the mixture is stirred evenly.
[0201] Example 8
[0202] The difference from Example 5 is that, in step one: 3) dispersant preparation, 0.011 mol of dimethyldiallylammonium chloride, acryloyloxyethyltrimethylammonium chloride and 0.0039 mol of vinyltrimethoxysilane in a mass ratio of 1:3.5 are mixed to form liquid A, 0.0145 mol of methacrylic acid, fumaric acid and 0.0022 mol of isopropanol in a mass ratio of 1:3.5 are mixed to form liquid B, and the mixture is stirred evenly.
[0203] Example 9
[0204] The difference from Example 5 is that, in step 1:
[0205] 1) mixing the titanium dioxide byproduct containing ferrous sulfate with water, heating and dissolving the mixture, adding 5% ammonia water for precipitation, filtering and removing impurities, and obtaining a ferrous solution with a ferrous ion mass fraction of 2 mol / L and a pH value of 3.0;
[0206] 2) Preparation of phosphorus source: industrial monoammonium phosphate is dissolved in phosphoric acid and water, filtered, and then 5% ammonia water is added to adjust the pH value to neutral to obtain a phosphorus source solution, wherein PO4 3- The content is 2mol / L;
[0207] 3) Dispersant preparation: 0.01 mol of dimethyldiallylammonium chloride, acryloyloxyethyltrimethylammonium chloride and 0.0031 mol of vinyltrimethoxysilane in a mass ratio of 1:3 were mixed to form liquid A; 0.014 mol of methacrylic acid, itaconic acid and 0.0017 mol of sodium hypophosphite in a mass ratio of 1:3 were mixed to form liquid B; and the mixture was stirred evenly;
[0208] 4) Based on 1 mol of iron, firstly, a ferrous source and a liquid A are mixed and added into a reactor as a base material, and then 15% of 1 mol of a phosphorus source solution and a liquid B are mixed, and 18% of a 3.4 mol hydrogen peroxide solution are slowly added dropwise to carry out a synthesis reaction. After the addition is completed, the mixture is stirred and reacted at 40° C. for 1 hour, and then the remaining phosphorus source is added at once. After stirring at 40° C. for 10 minutes, the remaining hydrogen peroxide solution is slowly added dropwise, and the reaction temperature is kept at no more than 40° C. After the addition is completed, the pH value is adjusted to 0.9 with phosphoric acid, and then the temperature is raised to 90° C. and the reaction is continued with stirring for 2.5 hours until the pH value is 1.6, and filter pressing, rinsing, flash evaporation, drying, crushing, and sieving are performed to obtain anhydrous ferric phosphate.
[0209] Example 10
[0210] The difference from Example 5 is that, in step 1:
[0211] 1) mixing the titanium dioxide byproduct containing ferrous sulfate with water, heating and dissolving the mixture, adding 15% ammonia water for precipitation, filtering and removing impurities, and obtaining a ferrous solution with a ferrous ion mass fraction of 2 mol / L and a pH value of 3.0;
[0212] 2) Preparation of phosphorus source: industrial monoammonium phosphate is dissolved in phosphoric acid and water, filtered, and then 15% ammonia water is added to adjust the pH value to neutral to obtain a phosphorus source solution, wherein PO4 3- The content is 2mol / L;
[0213] 3) Dispersant preparation: 0.01 mol of dimethyldiallylammonium chloride, acryloyloxyethyltrimethylammonium chloride and 0.0031 mol of vinyltrimethoxysilane in a mass ratio of 1:3 were mixed to form liquid A; 0.014 mol of methacrylic acid, itaconic acid and 0.0017 mol of sodium hypophosphite in a mass ratio of 1:3 were mixed to form liquid B; and the mixture was stirred evenly;
[0214] 4) Based on 1 mol of iron, firstly, a ferrous source and a liquid A are mixed and added into a reactor as a base material, and then 25% of a 1 mol phosphorus source solution and a liquid B are mixed, and 30% of a 3.4 mol hydrogen peroxide solution are slowly added dropwise to carry out a synthesis reaction. After the addition is completed, the mixture is stirred and reacted at 60° C. for half an hour, and then the remaining phosphorus source is added at once, and the mixture is stirred at 60° C. for 5 minutes, and then the remaining hydrogen peroxide solution is slowly added dropwise, and the reaction temperature is kept not exceeding 60° C. After the addition is completed, the pH value is adjusted to 1.5 with phosphoric acid, and then the temperature is raised to 95° C. and the reaction is continued with stirring for 1.5 hours until the pH value is 2.0, and filter pressing, rinsing, flash evaporation, drying, crushing, and sieving are performed to obtain anhydrous ferric phosphate.
[0215] Embodiment 11
[0216] The difference from Example 5 is that, in step 2:
[0217] The anhydrous iron phosphate prepared in step 1, 1 times the amount of lithium carbonate of the anhydrous iron phosphate substance, 0.8% of the mass of the anhydrous iron phosphate, yttrium oxide, titanium dioxide and cerium oxide in a mass ratio of 1:1:2, and 11.3% of the mass of the anhydrous iron phosphate in a mass ratio of 1:4 of propylene glycol and β-cyclodextrin, are added with pure water and stirred to form a slurry with a solid content of 48.0%, and the D50 particle size is adjusted to 0.42 μm by sand milling, and then spray-dried at a temperature higher than 215°C to control the D50 particle size to 4.5 μm; then heated to 760°C at 5°C / min in a nitrogen protective atmosphere, kept warm for 18 hours, cooled to below 100°C by air cooling, and crushed to obtain a lithium iron phosphate positive electrode material.
[0218] Example 12
[0219] The difference from Example 5 is that, in step 2:
[0220] The anhydrous iron phosphate prepared in step 1, 1.05 times the amount of lithium carbonate of the anhydrous iron phosphate substance, 0.9% of the mass of the anhydrous iron phosphate, yttrium oxide, manganese carbonate and cerium oxide in a mass ratio of 1:2:3, and 13.6% of the mass of the anhydrous iron phosphate, sodium gluconate and β-cyclodextrin in a mass ratio of 1:4, are added with pure water and stirred to form a slurry with a solid content of 48.0%. The D50 particle size is adjusted to 0.42 μm by sand milling, and then spray-dried at a temperature higher than 215° C. to control the D50 particle size to 4.5 μm; then, the mixture is heated to 820° C. at a rate of 5° C. / min in a nitrogen protective atmosphere, kept warm for 10 hours, cooled to below 100° C. by air cooling, and then crushed to obtain a lithium iron phosphate positive electrode material.
[0221] Example 13
[0222] The difference from Example 5 is that, in step 2:
[0223] The anhydrous iron phosphate prepared in step 1, 1.03 times the amount of lithium carbonate of the anhydrous iron phosphate substance, 0.83% of the mass of the anhydrous iron phosphate, yttrium oxide, boron trioxide and cerium oxide in a mass ratio of 1:1:3, and 13.2% of the mass of the anhydrous iron phosphate in a mass ratio of 1:4 of propylene glycol and β-cyclodextrin, are added with pure water and stirred to form a slurry with a solid content of 48.0%, and the D50 particle size is adjusted to 0.40 μm by sand milling, and then spray-dried at a temperature higher than 215°C to control the D50 particle size to 4.5 μm; then heated to 790°C at 5°C / min in a nitrogen protective atmosphere, kept warm for 14 hours, cooled to below 100°C by air cooling, and crushed to obtain a lithium iron phosphate positive electrode material.
[0224] Comparative Example 1
[0225] The comparative example provides a method for preparing anhydrous iron phosphate and a positive electrode material, which are prepared by the following method:
[0226] Step 1: 1) mixing the titanium dioxide byproduct with ferrous sulfate with water, heating and dissolving, adding 5% ammonia water for precipitation, filtering and removing impurities, and obtaining a ferrous solution with a ferrous ion mass fraction of 1.5 mol / L and a pH value of 2.8;
[0227] 2) Preparation of phosphorus source: industrial monoammonium phosphate is dissolved in phosphoric acid and water, filtered, and then 5% ammonia water is added to adjust the pH value to neutral to obtain a phosphorus source solution, wherein PO4 3- The content is 2mol / L;
[0228] 3) Based on 1 mol of iron, a ferrous source is first added into the reaction kettle as a base material, and then a phosphorus source solution and 3.2 mol of hydrogen peroxide solution are slowly added dropwise at the same time to carry out a synthesis reaction, ensuring that the addition is completed within 1 hour and the reaction temperature is maintained at no more than 60° C. After the addition is completed, the pH value is adjusted to 1.2 with phosphoric acid, and then the temperature is raised to 95° C. and the reaction is continued with stirring for 2 hours until the pH value is 1.8, and then filter pressing, rinsing, flash evaporation, drying, crushing, and sieving are performed to obtain anhydrous ferric phosphate.
[0229] Step 2: Add pure water to the anhydrous iron phosphate prepared in step 1, 1.02 times the amount of lithium carbonate of the anhydrous iron phosphate substance, 0.86% of the mass of titanium dioxide of the anhydrous iron phosphate, and 11.8% of the mass of glucose monohydrate of the anhydrous iron phosphate, and stir to form a slurry with a solid content of 48.0%. After the D50 particle size is adjusted to 0.38 μm by sand milling, it is spray-dried at a temperature higher than 215°C to control the D50 particle size to 4.5 μm; then, it is heated to 786°C at 5°C / min in a nitrogen protective atmosphere, kept warm for 12 hours, cooled to below 100°C by air cooling, and crushed to obtain a lithium iron phosphate positive electrode material.
[0230] Comparative Example 2
[0231] The comparative example provides a method for preparing anhydrous iron phosphate and a positive electrode material, which are prepared by the following method:
[0232] Step 1: 1) mixing the titanium dioxide byproduct with ferrous sulfate with water, heating and dissolving, adding 5% ammonia water for precipitation, filtering and removing impurities, and obtaining a ferrous solution with a ferrous ion mass fraction of 2 mol / L and a pH value of 3.2;
[0233] 2) Preparation of phosphorus source: industrial monoammonium phosphate is dissolved in phosphoric acid and water, filtered, and then 5% ammonia water is added to adjust the pH value to neutral to obtain a phosphorus source solution, wherein PO4 3- The content is 2mol / L;
[0234] 3) Based on 1 mol of iron, a ferrous source is first added into a reaction kettle as a base material, and then 20% of 1 mol of a phosphorus source solution and 20% of a 3.2 mol hydrogen peroxide solution are slowly added dropwise at the same time for a synthesis reaction. After the addition is completed, the reaction is stirred for half an hour, and then the remaining phosphorus source is added at once. After continuing to stir for 5 minutes, the remaining hydrogen peroxide solution is slowly added dropwise, and the reaction temperature is kept not higher than 60° C. After the addition is completed, the pH value is adjusted to 1.2 with phosphoric acid, and then the temperature is raised to 95° C. and the reaction is continued with stirring for 2 hours until the pH value is 1.8, and filter pressing, rinsing, flash evaporation, drying, crushing, and sieving are performed to obtain anhydrous ferric phosphate.
[0235] Step 2: Add pure water to the anhydrous iron phosphate prepared in step 1, 1.02 times the amount of lithium carbonate of the anhydrous iron phosphate substance, 0.86% of the mass of titanium dioxide of the anhydrous iron phosphate, and 11.8% of the mass of glucose monohydrate of the anhydrous iron phosphate, and stir to form a slurry with a solid content of 48.0%. After the D50 particle size is adjusted to 0.38 μm by sand milling, it is spray-dried at a temperature higher than 215°C to control the D50 particle size to 4.5 μm; then, it is heated to 786°C at 5°C / min in a nitrogen protective atmosphere, kept warm for 12 hours, cooled to below 100°C by air cooling, and crushed to obtain a lithium iron phosphate positive electrode material.
[0236] Comparative Example 3
[0237] The comparative example provides a method for preparing anhydrous iron phosphate and a positive electrode material, which are prepared by the following method:
[0238] Step 1: 1) mixing the titanium dioxide byproduct with ferrous sulfate with water, heating and dissolving, adding 5% ammonia water for precipitation, filtering and removing impurities, and obtaining a ferrous solution with a ferrous ion mass fraction of 2 mol / L and a pH value of 3.0;
[0239] 2) Preparation of phosphorus source: industrial monoammonium phosphate is dissolved in phosphoric acid and water, filtered, and then 5% ammonia water is added to adjust the pH value to neutral to obtain a phosphorus source solution, wherein PO4 3- The content is 2mol / L;
[0240] 3) Based on 1 mol of iron, a ferrous source is first added to the reactor as a base material, and then 25% of 1 mol of phosphorus source solution and 20% of 3.4 mol of hydrogen peroxide solution are slowly added dropwise at the same time for a synthesis reaction. After the addition is completed, the reaction is stirred for half an hour, and then the remaining phosphorus source is added at once. After continuing to stir for 5 minutes, the remaining hydrogen peroxide solution is slowly added dropwise, and the reaction temperature is kept not higher than 60° C. After the addition is completed, the pH value is adjusted to 1.0 with phosphoric acid, and then the temperature is raised to 95° C. and the reaction is continued with stirring for 2 hours until the pH value is 1.8, and filter pressing, rinsing, flash evaporation, drying, crushing, and sieving are performed to obtain anhydrous ferric phosphate.
[0241] Step 2: Add pure water to the anhydrous iron phosphate prepared in step 1, 1.02 times the amount of lithium carbonate of the anhydrous iron phosphate substance, 0.86% of the mass of titanium dioxide of the anhydrous iron phosphate, and 11.8% of the mass of glucose monohydrate of the anhydrous iron phosphate, and stir to form a slurry with a solid content of 48.0%. After the D50 particle size is adjusted to 0.38 μm by sand milling, it is spray-dried at a temperature higher than 215°C to control the D50 particle size to 4.5 μm; then, it is heated to 786°C at 5°C / min in a nitrogen protective atmosphere, kept warm for 12 hours, cooled to below 100°C by air cooling, and crushed to obtain a lithium iron phosphate positive electrode material.
[0242] Comparative Example 4
[0243] The comparative example provides a method for preparing anhydrous iron phosphate and a positive electrode material, which are prepared by the following method:
[0244] Step 1: 1) mixing the titanium dioxide byproduct with ferrous sulfate with water, heating and dissolving, adding 5% ammonia water for precipitation, filtering and removing impurities, and obtaining a ferrous solution with a ferrous ion mass fraction of 2 mol / L and a pH value of 3.0;
[0245] 2) Preparation of phosphorus source: industrial monoammonium phosphate is dissolved in phosphoric acid and water, filtered, and then 5% ammonia water is added to adjust the pH value to neutral to obtain a phosphorus source solution, wherein PO4 3- The content is 2mol / L;
[0246] 3) Based on 1 mol of iron, a ferrous source is first added into a reactor as a base material, and then 25% of 1 mol of a phosphorus source solution and 20% of a 3.4 mol hydrogen peroxide solution are slowly added dropwise at the same time for a synthesis reaction. After the addition is completed, the reaction is stirred for half an hour, and then the remaining phosphorus source is added at once. After continuing to stir for 5 minutes, the remaining hydrogen peroxide solution is slowly added dropwise, and the reaction temperature is kept not higher than 60° C. After the addition is completed, the pH value is adjusted to 1.0 with phosphoric acid, and then the temperature is raised to 95° C. and the reaction is continued with stirring for 2 hours until the pH value is 1.8, and filter pressing, rinsing, flash evaporation, drying, crushing, and sieving are performed to obtain anhydrous ferric phosphate.
[0247] Step 2: The anhydrous iron phosphate prepared in step 1, 1.03 times the amount of lithium carbonate of anhydrous iron phosphate, 0.86% of the mass of anhydrous iron phosphate, yttrium oxide, titanium dioxide and cerium oxide in a mass ratio of 1:2:3, 11.8% of the mass of anhydrous iron phosphate, propylene glycol and β-cyclodextrin in a mass ratio of 1:4 are added with pure water and stirred to form a slurry with a solid content of 48.0%, and the D50 particle size is adjusted to 0.40 μm by sand milling, and then spray dried at a temperature above 215°C to control the D50 particle size to 4.5 μm; then heated to 786°C at 5°C / min in a nitrogen protective atmosphere, kept warm for 16 hours, cooled to below 100°C by air cooling, and crushed to obtain a lithium iron phosphate positive electrode material.
[0248] Comparative Example 5
[0249] The comparative example provides a method for preparing anhydrous iron phosphate and a positive electrode material, which are prepared by the following method:
[0250] Step 1: 1) mixing the titanium dioxide byproduct with ferrous sulfate with water, heating and dissolving, adding 5% ammonia water for precipitation, filtering and removing impurities, and obtaining a ferrous solution with a ferrous ion mass fraction of 2 mol / L and a pH value of 3.0;
[0251] 2) Preparation of phosphorus source: industrial monoammonium phosphate is dissolved in phosphoric acid and water, filtered, and then 5% ammonia water is added to adjust the pH value to neutral to obtain a phosphorus source solution, wherein PO4 3- The content is 2mol / L;
[0252] 3) Based on 1 mol of iron, a ferrous source is first added into a reactor as a base material, and then 25% of 1 mol of a phosphorus source solution and 20% of a 3.4 mol hydrogen peroxide solution are slowly added dropwise at the same time for a synthesis reaction. After the addition is completed, the reaction is stirred for half an hour, and then the remaining phosphorus source is added at once. After continuing to stir for 5 minutes, the remaining hydrogen peroxide solution is slowly added dropwise, and the reaction temperature is kept not higher than 60° C. After the addition is completed, the pH value is adjusted to 1.0 with phosphoric acid, and then the temperature is raised to 95° C. and the reaction is continued with stirring for 2 hours until the pH value is 1.8, and filter pressing, rinsing, flash evaporation, drying, crushing, and sieving are performed to obtain anhydrous ferric phosphate.
[0253] Step 2: The anhydrous iron phosphate prepared in step 1, 1.03 times the amount of lithium carbonate of anhydrous iron phosphate, 0.83% of the mass of anhydrous iron phosphate, yttrium oxide, titanium dioxide and cerium oxide in a mass ratio of 2:3:5, 12.7% of the mass of anhydrous iron phosphate, propylene glycol and β-cyclodextrin in a mass ratio of 1:4 are added with pure water and stirred to form a slurry with a solid content of 48.0%, and the D50 particle size is adjusted to 0.42 μm by sand milling, and then spray-dried at a temperature above 215°C to control the D50 particle size to 4.5 μm; then heated to 788°C at 5°C / min in a nitrogen protective atmosphere, kept warm for 14 hours, cooled to below 100°C by air cooling, and crushed to obtain a lithium iron phosphate positive electrode material.
[0254] Comparative Example 6
[0255] The comparative example provides a method for preparing anhydrous iron phosphate and a positive electrode material, which are prepared by the following method:
[0256] Step 1: 1) mixing the titanium dioxide byproduct with ferrous sulfate with water, heating and dissolving, adding 5% ammonia water for precipitation, filtering and removing impurities, and obtaining a ferrous solution with a ferrous ion mass fraction of 2 mol / L and a pH value of 3.0;
[0257] 2) Preparation of phosphorus source: industrial monoammonium phosphate is dissolved in phosphoric acid and water, filtered, and then 5% ammonia water is added to adjust the pH value to neutral to obtain a phosphorus source solution, wherein PO4 3- The content is 2mol / L;
[0258] 3) Based on 1 mol of iron, a ferrous source is first added into a reactor as a base material, and then 25% of 1 mol of a phosphorus source solution and 20% of a 3.4 mol hydrogen peroxide solution are slowly added dropwise at the same time for a synthesis reaction. After the addition is completed, the reaction is stirred for half an hour, and then the remaining phosphorus source is added at once. After continuing to stir for 5 minutes, the remaining hydrogen peroxide solution is slowly added dropwise, and the reaction temperature is kept not higher than 60° C. After the addition is completed, the pH value is adjusted to 1.0 with phosphoric acid, and then the temperature is raised to 95° C. and the reaction is continued with stirring for 2 hours until the pH value is 1.8, and filter pressing, rinsing, flash evaporation, drying, crushing, and sieving are performed to obtain anhydrous ferric phosphate.
[0259] Step 2: The anhydrous iron phosphate prepared in step 1, 1.03 times the amount of lithium carbonate of anhydrous iron phosphate, 0.83% of the mass of anhydrous iron phosphate, yttrium oxide, titanium dioxide and cerium oxide in a mass ratio of 2:3:5, 13.2% of the mass of anhydrous iron phosphate, propylene glycol and β-cyclodextrin in a mass ratio of 1:4 are added with pure water and stirred to form a slurry with a solid content of 48.0%, and the D50 particle size is adjusted to 0.40 μm by sand milling, and then spray-dried at a temperature above 215°C to control the D50 particle size to 4.5 μm; then heated to 790°C at 5°C / min in a nitrogen protective atmosphere, kept warm for 14 hours, cooled to below 100°C by air cooling, and crushed to obtain a lithium iron phosphate positive electrode material.
[0260] 2. Test Method
[0261] 1. Property test of anhydrous iron phosphate and positive electrode materials
[0262] 1) SEM test: Scanning electron microscopy analysis, JSM6390 scanning electron microscope, using NanoMeasurer software to analyze the primary particle size and distribution.
[0263] 2) XRD test: X-ray diffraction analysis (XRD) is used to determine the composition and content of the phase in the sample. This test uses the Empyrean rotating anode X-ray diffractometer from PANalytical, the Netherlands.
[0264] 3) Sphericity: According to the SEM image, the overall particles are distributed between ellipses and spheres, and the sphericity is calculated (the sphericity of a tetrahedron is 0.908, and the sphericity of a sphere is 1).
[0265] 4) Tap density: tested with a tap density meter with 5000 vibrations.
[0266] 5) Compaction density test: Use a compaction density meter to test, the test pressure is 3T, and the pressing time is 30S.
[0267] 6) Iron-phosphorus ratio: The iron content is determined by the potassium dichromate method, and the phosphorus content is determined by the quinoline phosphomolybdate weighing method. The iron-phosphorus ratio is the ratio of the amount of iron to the amount of phosphorus.
[0268] 7) BET specific surface area: A Micromeritics surface area analyzer (TriStar II 3020, micromeritics) was used. Nitrogen was used as the adsorbent and helium or hydrogen was used as the carrier gas. The two gases were mixed in a certain ratio to reach a specified relative pressure and then flowed through the solid material. By changing the mixing ratio of nitrogen and carrier gas, the adsorption amount under several relative pressures of nitrogen can be measured, and the specific surface area can be calculated according to the BET specific surface area formula. A 2 g sample was degassed and dried at 120°C for 2 h and then tested in a Dewar flask filled with liquid nitrogen.
[0269] 8) Carbon content test: Infrared carbon sulfur analyzer, model HCS-140, Shanghai Dekai Instrument Co., Ltd.
[0270] 2. Properties test of secondary batteries
[0271] Lithium iron phosphate gram capacity test: Blue electricity test, using the prepared material as the positive electrode material, acetylene black as the conductive agent, polytetrafluoroethylene as the binder, and making the electrode sheet at a mass ratio of 90:5:5, with metal lithium as the negative electrode, assembled into a CR2032 button battery. Test 1C charge-discharge at 2V~3.75V, 25±0.5℃, and 1P constant power charge-discharge at 2.5V~3.75V, 25±0.5℃.
[0272] III. Analysis of test results of various embodiments and comparative examples
[0273] The tap density of the anhydrous iron phosphate and the compacted density of lithium iron phosphate prepared in the examples and comparative examples are shown in Tables 1 and 2, and the electrochemical performance test results are shown in Table 3.
[0274] Table 1
[0275]
[0276]
[0277] Table 2
[0278]
[0279]
[0280] Table 3
[0281]
[0282] By comparing the data in Table 1 and Table 2, it can be found that the compaction density of spherical anhydrous iron phosphate prepared by the embodiment through the formation of surfactant-like anionic monomers and cationic monomers is higher, and the compaction density of lithium iron phosphate prepared by using this anhydrous iron phosphate is higher, indicating that the addition of the first dispersant and the second dispersant can effectively regulate the crystal morphology. The preparation method of the present application can ensure that the particle size distribution of the prepared lithium iron phosphate is more reasonable, which is conducive to the preparation of lithium iron phosphate positive electrode materials with high compaction density and good electrical properties.
[0283] By comparing the data in Table 3, it can be found that the charging performance of lithium iron phosphate 1C prepared in the embodiment and the comparative example is similar, but the discharge efficiency of the comparative example is significantly lower, and the constant power charging and discharging performance of the comparative example 1P is significantly worse. Combining the lithium iron phosphate particle size distribution in Table 1 and Table 2, it can be seen that the addition of the first dispersant and the second dispersant can effectively regulate the crystal morphology of anhydrous iron phosphate, thereby controlling the primary particle size distribution and morphology of lithium iron phosphate, and improving the carbon coating effect and electrochemical properties of lithium iron phosphate. Among them, the compaction density and electrochemical performance of Example 5 are the best, which is related to its better crystal morphology and primary particle size distribution.
[0284] The anhydrous ferric phosphate obtained in Example 5 and Comparative Example 5 was observed for morphology, and the SEM images (scanning electron microscope images) of the two were as follows: Figure 1 and Figure 2 As shown, the XRD comparison diagram is as follows Figure 3 As shown, Figure 3 The image in the upper middle part is an enlargement of the lower part to better compare the diffraction peak positions and heights.
[0285] The SEM images and primary particle size distribution analysis of the lithium iron phosphate obtained in Example 5 and Comparative Example 5 are as follows: Figure 4 and Figure 5 shown.
[0286] Depend on Figure 1 , Figure 2 It can be seen that the anhydrous ferric phosphate prepared by adding the first dispersant and the second dispersant in Example 5 has a higher sphericity, while the anhydrous ferric phosphate prepared in Comparative Example 5 tends to grow in a long strip shape without adding any dispersant. Comparison of Table 1 and Table 2 shows that the anhydrous ferric phosphate prepared by adding the first dispersant and the second dispersant in Example 5 has a smaller BET specific surface area and a higher compacted density.
[0287] Depend on Figure 3 XRD comparative analysis found that the XRD diffraction peak of the anhydrous iron phosphate prepared in Example 5 was stronger, and the XRD diffraction peak of the anhydrous iron phosphate prepared in Comparative Example 5 was obviously left-biased and had more impurity peaks, indicating that the first dispersant and the second dispersant were beneficial to promoting the formation of anhydrous iron phosphate and regulating the crystal growth morphology of anhydrous iron phosphate.
[0288] contrast Figure 4 , Figure 5 From the SEM images and particle size distribution analysis, it was found that the lithium iron phosphate spheres prepared in the embodiment using the anhydrous iron phosphate prepared by adding the first dispersant and the second dispersant as raw material had better shape, a higher proportion of particles with a diameter within 200 nm, and a higher compaction density corresponding to Tables 1 and 2, indicating that the addition of the first dispersant and the second dispersant can effectively regulate the morphology of anhydrous iron phosphate, thereby controlling the morphology and compaction density of lithium iron phosphate and improving the electrochemical properties of lithium iron phosphate.
[0289] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.
Claims
1. Anhydrous ferric phosphate, characterized in that: In terms of weight percentage, among the primary particles of the anhydrous ferric phosphate, the number of particles with a particle size greater than or equal to 0.01 μm and less than 0.1 μm accounts for 10% to 30%, the number of particles with a particle size of 0.1 μm to 0.2 μm accounts for 50% to 60%, the number of particles with a particle size greater than 0.2 μm and less than 0.4 μm accounts for 15% to 30%, and the number of particles with a particle size of 0.4 μm to 0.6 μm accounts for 0.2% to 10%.
2. The anhydrous ferric phosphate according to claim 1, characterized in that The particle shape of the anhydrous ferric phosphate is spherical, and the sphericity is 0.84-0.98; the tap density of the anhydrous ferric phosphate is 0.93 g / cm 3 ~1.13g / cm 3 , compacted density is 1.57g / cm 3 ~1.61g / cm 3 , the iron-phosphorus ratio is (0.957~0.970):
1.
3. A method for preparing anhydrous ferric phosphate, characterized in that: include: Mixing a ferrous source with a first dispersant to obtain a first raw material liquid; mixing the first phosphorus source and the second dispersant to obtain a second raw material solution; The first raw material liquid, the second raw material liquid and a first oxidant are mixed, and after a first reaction treatment, a first mixture is obtained; Adding a second phosphorus source to the first mixture, and after a second reaction treatment, adding a second oxidant to obtain a second mixture; Adjusting the pH value and temperature of the second mixture, and obtaining the anhydrous ferric phosphate after the third reaction treatment; The first dispersant includes a cationic monomer and a coupling agent, and the second dispersant includes an anionic monomer and a chain transfer agent.
4. The method for preparing anhydrous ferric phosphate according to claim 3, characterized in that: The cationic monomer includes dimethyldiallylammonium chloride and / or acryloyloxyethyltrimethylammonium chloride; And / or, the coupling agent includes vinyltrimethoxysilane and / or 3-(methacryloyloxy)propyltrimethoxysilane; When the cationic monomer includes dimethyldiallyl ammonium chloride and acryloyloxyethyltrimethylammonium chloride, the mass ratio of dimethyldiallyl ammonium chloride to acryloyloxyethyltrimethylammonium chloride is 1:(2.5-3.5); and / or, The anionic monomer includes one or more of methacrylic acid, itaconic acid and fumaric acid; And / or, the chain transfer agent comprises sodium hypophosphite and / or isopropyl alcohol; When the anionic monomer includes methacrylic acid and itaconic acid, the mass ratio of methacrylic acid to itaconic acid is 1:(2.5-3.5); when the anionic monomer includes methacrylic acid and fumaric acid, the mass ratio of methacrylic acid to fumaric acid is 1:(2.5-3.5); and / or, The molar ratio of the cationic monomer to the coupling agent is 100:(20-35); and / or, The molar ratio of the anionic monomer to the chain transfer agent is 100:(10-15).
5. The method for preparing anhydrous ferric phosphate according to claim 3 or 4, characterized in that: The molar ratio of the iron element in the ferrous source to the first dispersant is 1:(0.0125-0.0150); and / or, The molar ratio of the iron element in the ferrous source to the phosphorus element in the phosphorus source is 1:(0.9-1.1); and / or, The molar ratio of phosphorus in the phosphorus source to the second dispersant is 1:(0.0150-0.0170); And / or, the ferrous source is prepared by the following method: mixing a titanium dioxide byproduct having ferrous sulfate with water, heating and dissolving the mixture, adding 5% to 15% ammonia water by mass for precipitation, filtering and retaining the filtrate to obtain the ferrous source; And / or, independently, the first phosphorus source and the second phosphorus source are prepared by the following method: dissolving monoammonium phosphate, phosphoric acid and water and filtering, and adding 5% to 15% ammonia water by mass to the filtrate to adjust the pH value to 6 to 8.
6. The method for preparing anhydrous ferric phosphate according to any one of claims 3 to 5, characterized in that: The first oxidant comprises hydrogen peroxide and / or sodium peroxide; and / or, The second oxidant comprises hydrogen peroxide and / or sodium peroxide; and / or, The mass ratio of the first phosphorus source to the second phosphorus source is (15-25): (75-85); and / or, The molar ratio of the iron element in the ferrous source to the first oxidant is 1:(0.6-1.1); and / or the molar ratio of the iron element in the ferrous source to the second oxidant is 1:(2.1-2.8).
7. The method for preparing anhydrous ferric phosphate according to any one of claims 3 to 6, characterized in that: In the first reaction treatment, the temperature is 40°C to 60°C and the time is 0.5h to 1h; and / or, In the second reaction treatment, the temperature is 40° C. to 60° C., and the time is 5 min to 10 min.
8. The method for preparing anhydrous ferric phosphate according to any one of claims 3 to 7, characterized in that: The step of adjusting the pH value and temperature of the second mixture to obtain the anhydrous ferric phosphate after the third reaction treatment comprises: Adjusting the temperature of the second mixture to 40° C. to 60° C., controlling the pH value of the second mixture to 0.9 to 1.5, raising the temperature to 90° C. to 95° C. to react until the pH value is 1.6 to 2.0, to obtain a third mixture; The third mixture is sequentially subjected to filter pressing, rinsing, flash evaporation, drying, crushing and sieving to obtain the anhydrous ferric phosphate.
9. A positive electrode material, characterized in that: The general formula of the positive electrode material is LiFe 1-a-b-c Y a Ce b M c PO4@C, wherein M is one or more of tin, titanium, boron, and manganese, a is 0.007 to 0.013, b is 0.029 to 0.057, and c is 0.01 to 0.033; and C accounts for 1.2% to 1.4% of the mass of the positive electrode material.
10. The positive electrode material according to claim 9, characterized in that The average primary particle size of the positive electrode material is 0.24 μm to 0.34 μm; Among them, in the positive electrode material, the number fraction of particles with an average primary particle size greater than or equal to 1 μm is less than or equal to 3.20%, and the compaction density is 2.52 g / cm 3 ~2.64g / cm 3 .
11. A method for preparing a positive electrode material, characterized in that: The following steps are involved: Mixing the anhydrous ferric phosphate according to claim 1 or 2, a lithium source, a carbon source, a complexing agent, a dopant and water to obtain a mixed material; The mixed material is sintered under a protective atmosphere to obtain the positive electrode material; The dopant comprises yttrium oxide, cerium oxide and other oxides, and the other oxides comprise one or more of tin oxide, titanium oxide, boron oxide and manganese oxide.
12. The method for preparing the positive electrode material according to claim 11, characterized in that: The complexing agent includes glycerol and / or sodium gluconate; and / or, The dopant comprises yttrium oxide, cerium oxide and the other oxide-containing materials, wherein the other oxide-containing materials comprise one or more of tin dioxide, titanium dioxide, boron trioxide and manganese carbonate; the mass ratio of the yttrium oxide, the cerium oxide and the other oxide-containing materials is 1:(2-3):(1-2); and / or, The mass ratio of the anhydrous ferric phosphate to the complexing agent is 1:(0.02-0.03); and / or, the mass ratio of the anhydrous ferric phosphate to the dopant is 1:(0.008-0.009); and / or, The mass ratio of the anhydrous ferric phosphate to the lithium source is 1:(1-1.05); and / or the mass ratio of the anhydrous ferric phosphate to the carbon source is 1:(0.09-0.11).
13. The method for preparing the positive electrode material according to claim 11 or 12, characterized in that: The step of sintering the mixed material under a protective atmosphere to obtain the positive electrode material comprises: The mixed material is ground to obtain a ground material, wherein the D50 particle size of the ground material is 0.38 μm to 0.42 μm; The ground material is spray-dried to obtain a spray material, wherein the D50 particle size of the spray material is 3.4 μm to 6.7 μm; The sprayed material is subjected to the sintering treatment under the protective atmosphere to obtain the positive electrode material; The sintering temperature is 760° C. to 820° C., and the sintering time is 10 h to 18 h.
14. A positive electrode sheet, characterized in that: The invention comprises a positive electrode current collector and a positive electrode active layer arranged on at least one side of the positive electrode current collector, wherein the positive electrode active layer comprises the positive electrode material according to claim 9 or 10.
15. A secondary battery, characterized in that: Including the positive electrode sheet as described in claim 14.
Citation Information
Cited By
High-energy density type lithium iron phosphate positive electrode material and preparation method thereof
CN120637450A
Lithium iron phosphate material and preparation method thereof, positive pole piece and secondary battery
CN121247755A